Temperature history determines the adult size and maturation rates in seasonal cohorts of Loligo forbesii squid - A.M. Power; M.A. Collins; A. Arkhipkin; S. Wangvoralak; M. Petroni; G.J. Pierce (Estuarine, Coastal and Shelf Science, 2026)

Oceanographic parameters associated with spatial occurrence of cephalopods in standardized demersal fishing trawls in the NE Atlantic - Daniel Oesterwind; Anne Marie Power; Esther Abad; Gregoire Certain; Nikolaos Fotiadis; Alexey Golikov; Ángel F. González; Vladimir Laptikhovsky; Silvia S. Monteiro; Carlos Montero-Castaño; Ana Moreno; Hassan Moustahfid; et al. (Marine Biology, 2026)
In this work, the environmental occurrence ranges of different European cephalopod species are described for the whole NE Atlantic shelf including the greater North Sea and Baltic Sea. This is done based on the environmental parameters collected in-situ during surveys that caught commercially important cephalopod species (1990–2022). Results are supplemented and compared with information available in the published literature and are discussed in relation to available habitat across the range, survey design, etc., and, in particular, which species are most likely to be affected by climate change. Our analyses illustrate that Loligo forbesii occupies a broader depth range than Loligo vulgaris and Alloteuthis spp. Because L. forbesii occurs further offshore and at greater depths, this species is likely more resilient to warming than the other loliginids in our study. Octopus vulgaris is documented in areas close to the coast with a more southerly distribution, whereas Eledone cirrhosa occurs further north and further away from the coast. Eledone cirrhosa occurs at lower temperatures and has a much broader depth range, which may provide resilience against warming. By contrast, both ommastrephid squid species ( Illex coindetii and Todaropsis eblanae ) showed a very similar tolerance to the three environmental variables (salinity, temperature, depth). This information should contribute to future species distribution modelling by allowing validation of realistic results against each species’ range, habitat requirements, and environmental ranges, while appreciating the data limitations caused by the timing and gear used in the survey cruises that supply occurrence and density data.

Freshwater biodiversity in a rapidly changing Arctic: An expert horizon scan of key research questions - Joseph M. Culp; Michael Power; Kirsten S. Christoffersen; Willem Goedkoop; Kimmo K. Kahilainen; Milla Rautio; Fernando Chaguaceda; Marie-Pier Hébert; Sanne M. Moedt; Dermot Antoniades; Simon Belle; Daniel Bolnick; et al. (Ambio, 2026)
Arctic freshwater biodiversity is rapidly changing due to climate warming, resource extraction, infrastructure development, and landscape transformation. To improve understanding, predict future responses, and inform policy formulation, research needs must be clearly identified. Using a horizon scan survey, Arctic freshwater experts from government, international agencies, and Indigenous Peoples identified 77 biodiversity research questions with 17 highlighted as most important for near term assessment. These questions span nine thematic categories: biodiversity and taxonomic challenges, hydrological change, productivity and food webs, ecosystem connectivity, methods, monitoring and assessment, permafrost change, winter ecology, anthropogenic development, and Indigenous Knowledge. Climate change emerged as the major driver among all categories and research questions. A key priority identified was the urgent need for long-term, harmonized monitoring programs among Arctic countries. Multiple knowledge gaps detected suggest that circumpolar research collaborations are required to tackle these issues.

Nutrient Enrichment Increases Grassland Biomass Sensitivity to Interannual Precipitation Variation - Ingrid J. Slette; Eric W. Seabloom; Carlos Alberto Arnillas; Jonathan D. Bakker; Dana Blumenthal; Jane A. Catford; Scott L. Collins; Nico Eisenhauer; Philip A. Fay; Magda Garbowski; Sylvia Haider; W. Stanley Harpole; et al. (Global Change Biology, 2026)
Primary production underpins much of ecosystem functioning and is often limited by nutrient and water availability. Ongoing global increases in nutrient inputs and interannual precipitation variability are thus likely to impact primary production, with unclear consequences for interannual variability in plant biomass. We used data from 35 grasslands in the Nutrient Network coordinated fertilization experiment to test if nutrient addition alters the response of plant biomass to year‐to‐year variation in growing season precipitation, and whether the effects of nutrient addition vary with factors such as site aridity or plant community composition. Nutrient addition increased biomass (by an average of 46% across sites), rain‐use efficiency (by 48%), and the sensitivity of biomass to interannual variation in precipitation (i.e., larger increase in biomass in wet years; by 13%), but did not change the strength of the interannual precipitation‐biomass correlation. Both sensitivity and correlation strength were higher in more arid sites, regardless of nutrient addition. These results suggest that grassland ecosystem functioning may become more variable from year to year as nutrient enrichment increases biomass sensitivity to precipitation and precipitation becomes more variable.

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Impacts of nature relatedness and motivation on active outdoor recreation participation - Megan K. McCabe; Sammie L. Powers; Julie S. Son (Journal of Outdoor Recreation and Tourism, 2026)

Millennial-scale fire and climate dynamics in the world's largest tropical wetland show emerging fire threat to flooded ecosystems - Bronwen S. Whitney; Danilo M. Neves; Nicholas J.D. Loughlin; Carlos D'Apolito; Carla Coblinski Tavares; Emma P. Hocking; Francis E. Mayle; Mitchell J. Power; Aguinaldo Silva; Mario L. Assine (Global and Planetary Change, 2026)

Retrogressive Thaw Slumps Produce a Changing Disturbance Regime for Arctic Stream Invertebrates - Maria Dolan; Jordan Musetta‐Lambert; Krista S. Chin; Steven V. Kokelj; Suzanne E. Tank; Jennifer Lento; Michael Power; Joseph M. Culp (Global Change Biology, 2026)
For many Arctic rivers and streams, climate‐driven intensification of permafrost thaw slumping is a major source of disturbance to aquatic habitats. Thaw slumps are dynamic landforms that severely increase total suspended solids (TSS) and nutrients in downstream reaches and can persist over decades. Effects may differ in magnitude as slumps cycle through periods of higher and lower activity, with expansion of retrogressive slumps increasing over time. Increases in TSS are known to cause reduced invertebrate abundance and diversity in impacted watersheds; however, it remains unclear if water quality and critical aquatic biodiversity have recovered after prolonged exposure to slumps. Here, we examined decadal‐scale effects of slumps and environmental change on benthic macroinvertebrates (BMI) by comparing environmental and BMI data collected between 2010–2014 and a recent sampling campaign from 2021. High TSS and nutrient concentrations observed during 2010–2014 persisted in slump‐impacted sites in 2021, with no significant change in TSS and total nutrient concentrations after the 10‐year exposure period. TSS continued to act as a nonspecific stressor on BMI, as abundance remained significantly lower in impacted streams compared to reference streams. Although total abundance within reference and impacted sites did not differ significantly between sampling periods, abundance and richness of disturbance tolerant taxa was greater in 2021 as compared to 2010–2014 across all sites, with differences linked to lower precipitation in 2021. These community compositional changes were reflected in increased Shannon‐Weiner diversity between sampling campaigns. Overall, the number of thaw slumps upstream was an important driver of both BMI abundance and diversity across sampling periods and will likely continue to be an important determinant of benthic macroinvertebrate communities as the number and size of thaw slumps continues to increase across the circumpolar Arctic.

Unveiling the hidden consequences of mining tailings on ecosystem processes: Disruption of decomposition of native species in the Rio Doce watershed - João Carlos Figueiredo; Yule Roberta Ferreira Nunes; Walisson Kenedy-Siqueira; Renata Maia; Yumi Oki; Milton Barbosa; Débora Lima-Santos; Flávio Mariano Machado Mota; Daniel Negreiros; Letícia Ramos; Marcos Paulo dos Santos; Rebeca Ferreira Reis; et al. (Forest Ecology and Management, 2026)

Incorporating enhanced rock weathering into sustainable forest management - Minger Guo; Ian M. Power; Shaun A. Watmough; Adam S. Gorgolewski; Larissa M.M. Wallisch; Jonathan Spence; Sasha Wilson (Journal of Environmental Management, 2025)

Development of a fipronil insecticide response spectrum model for juvenile Chinook salmon (Oncorhynchus tshawytscha) - Kara E. Huff Hartz; Katie J. Knaub; Louise Cominassi; Giovanni S. Molinari; Shane Power; Mia Arkles; S.D.M. Chinthaka; Andrea Chandler; Md. Habibullah-Al-Mamun; Gregory Whitledge; Amelie Segarra; Richard E. Connon; et al. (Environmental Pollution, 2025)

Improving Access to Care: Leveraging Virtual Weight Management Education Groups for New Patients in Rural and Suburban Communities - J. Powers; J. Fisher; S. Coolbaugh; A. Zammit; R. Dumont; S. Cortese (Journal of the Academy of Nutrition and Dietetics, 2025)

The efficacy and ecological impact of mercury sorbents on the physiology and reproductive fitness of Daphnia magna - S. Power; A. Minet; P. Ku; A. Sexton; P.G. Matson; J.P. Marquardt; Z.W. Clark; A. Johs; T.J. Mathews; L.M. Stevenson (Journal of Hazardous Materials, 2025)

Using a critical body residue approach to assess the acute toxicity of a pesticide mixture to juvenile Chinook salmon (Oncorhynchus tshawytscha) - Kara E. Huff Hartz; Mia Arkles; Katie J. Knaub; Shane D. Power; Giovanni S. Molinari; S.D.M. Chinthaka; Gregory Whitledge; Amelie Segarra; Richard E. Connon; Shawn Acuña; Michael J. Lydy (Environmental Pollution, 2025)

Fishery-independent camera surveys provide novel observations of white sharks (Carcharodon carcharias) off coastal Alabama - J. Marcus Drymon; Amanda E. Jargowsky; Theodore S. Switzer; Crystal L. Hightower; Sean P. Powers (Frontiers in Marine Science, 2025)
Determining the distributions of marine animals is a challenge, particularly for highly migratory species like sharks. In the United States, several shark populations are beginning to recover following exploitation, including the white shark ( Carcharodon carcharias ). Recently, reports of white sharks have increased in the northern Gulf of Mexico (hereafter Gulf), but determining whether these reports represent actual changes in distribution is difficult. Therefore, we examined two long-term fishery-independent camera datasets to assess whether the recent increase in reports of white sharks reflects changes in distribution or typical (albeit rare) events. Long-term fishery-independent stereo-baited remote underwater video (sBRUV) and remotely operated vehicle (ROV) datasets were examined. From 2010 – 2024, 8368 sBRUV and 2199 ROV surveys were conducted. From 2010 – 2023, no white sharks were seen on either camera gear, but two white sharks were observed on ROV videos in 2024. The first was a female estimated at 239 cm total length and the second was a male estimated at 191 cm total length. These observations lend support to the notion that recent reports of white sharks in the northern Gulf may indicate early evidence of range-edge expansion rather than increases in telemetry efforts or citizen observations. Studies like this one highlight the value of long-term, randomized, fishery-independent camera surveys for documenting changes in distribution for rare species.

A balanced approach to the potential of octopus aquaculture - Ian G. Gleadall; Roger Villanueva; Gregory J. Barord; Zoe Doubleday; Felipe Aguado-Giménez; Nobuhiko Akiyama; Eduardo Almansa; Cheryl L. Ames; Alexander Arkhipkin; Otilio Avendaño; Chris Barrett; Giambattista Bello; et al. (Marine Policy, 2025)

Assessing the chemical burden of the North-East Atlantic ecosystem through targeted and untargeted HRMS-based approaches - Georgios Gkotsis; Maria-Christina Nika; Nikiforos Alygizakis; Konstantinos Vasilatos; Antonia Athanasopoulou; Jonathan L. Barber; Rob Berbee; Thierry Burgeot; Susana Galante Oliveira; Johan Gustafsson; Alejandro Iglesias Campos; Ulrike Kammann; et al. (Journal of Hazardous Materials, 2025)

TropiRoot 1.0: Database of tropical root characteristics across environments - Amanda L. Cordeiro; Daniela F. Cusack; Nathaly Guerrero‐Ramírez; Richard J. Norby; Laura Toro; Michelle Y. Wong; S. Joseph Wright; Kristine Grace M. Cabugao; Kelly M. Andersen; Lucia Fuchslueger; Colleen M. Iversen; Fiona Soper; et al. (Ecology, 2025)
Tropical ecosystems contain the world's largest biodiversity of vascular plants. Yet, our understanding of tropical functional diversity and its contribution to global diversity patterns is constrained by data availability. This discrepancy underscores an urgent need to bridge data gaps by incorporating comprehensive tropical root data into global datasets. Here, we provide a database of tropical root characteristics. This new database, TropiRoot 1.0, will be instrumental in evaluating an array of hypotheses pertaining to root functional ecology and plant biogeography, both within the tropics and relative to other global biomes. The data compilation was conducted by the TropiRoot Initiative, in partnership with the Fine‐Root Ecology Database (FRED) and the Global Root Trait (GRooT) database, Colorado State University (CSU) and the Smithsonian Tropical Research Institute (STRI). Literature search and data extraction were conducted between 2020 and 2024. Literature was identified using Web of Science, Scopus, and complemented using the expert knowledge of members of TropiRoot. To provide broad environmental and geographical distributions, literature searches included root characteristics (traits) across global change drivers, natural gradients, and from different continents. We adopted FRED standardized data columns and streamlined the format to enhance accessibility for data extraction across various user groups. This optimized framework resulted in a smaller, yet comprehensive datasheet. To make the database compatible with other global root trait initiatives, column identification was standardized following the codes provided by FRED. These efforts culminated in data extracted from 104 new sources, resulting in more than 8000 rows of data (either species or community data). Most of the data in TropiRoot 1.0 include root characteristics such as root biomass, morphology, root dynamics, mass fraction, architecture, anatomy, physiology, and root chemistry. This initiative represents a 30% increase in the currently available data for tropical roots in FRED. TropiRoot 1.0 contains root characteristics from 25 different countries, where seven are located in Asia, six in South America, five in Central America and the Caribbean, four in Africa, two in North America, and 1 in Oceania. Due to the volume of data, when ancillary data were available, including soil data, these data were either extracted and included in the database or its availability was recorded in an additional column. Multiple contributors checked the entries for outliers during the collation process to ensure data quality. For text‐based observations, we examined all cells to ensure that their content relates to their specific categories. For numerical observations, we ordered each numerical value from least to greatest and plotted the values, checking apparent outliers against the data in their respective sources and correcting or removing incorrect or impossible values. Some data (soil and aboveground) have different columns for the same variable presented in different units, including originally published units, but root characteristics data had units converted to match those reported in FRED. By filling a gap from global databases, TropiRoot 1.0 expands our knowledge of otherwise so far underrepresented regions and our ability to assess global trends. This advancement can be used to improve tropical forest representation in vegetation models. The data are freely available and should be cited when used.

A social switch: daylength drives meadow vole group dynamics in automatically tracked habitats - Kelley C. Power; Nicole S. Lee; Kayla Rendon-Torres; David A.W. Soergel; Annaliese K. Beery (Animal Behaviour, 2025)

The nature of microbial diversity and assembly in the Nebraska Sandhills depends on organismal identity and habitat type - Kaitlin Gattoni; Eli M. S. Gendron; J. Parr McQueen; Kirsten Powers; Thomas O. Powers; Mary J. Harner; Jessica R. Corman; Dorota L. Porazinska (Community Ecology, 2025)

Carbon production at shallow‐water artificial reef ecosystems relies on water column primary productivity - Traci Erin Cox; Kelly S. Boyle; Mark A. Albins; Sean P. Powers; Just Cebrian (Limnology and Oceanography, 2025)
The attraction‐production continuum in fishery management centers on the extent to which artificial reefs increase fish production or whether they simply redistribute fish. Reef systems could produce carbon to support growth of higher trophic levels. Therefore, we aimed to understand carbon flows at lower trophic levels on shallow‐water (11 m) artificial reefs within a region which hosts an extensive artificial reef network. We described benthic communities and quantified changes in oxygen content within in situ enclosures to assess reef, sediment, and water‐column community metabolism. We tested spatial and temporal differences in metrics by repeatedly sampling at three sites across two seasons for 2 yrs. Suspension feeders were abundant on reef surfaces and these communities were often heterotrophic. In sediments, lancelets, amphipods, and bivalves were scarcer adjacent to the reef (2 m) and more numerous 20 m away. Infauna communities at adjacent reefs were significantly dissimilar, suggesting biotic (e.g., predation) and, or abiotic (e.g., sand scour) conditions cause large differences in infauna communities near reefs. Sediment and water‐column communities were mostly autotrophic and net productivity did not consistently increase or decrease with distance from the reef. Metabolic metrics were often best explained by temporal intervals and site. The integrated system was autotrophic in 9 out of 11 instances where reef, sediment, and water‐column contributed −0.46 to 0.27, −14.8 to 66.8, and 33.5% to 91.4% respectively to net system productivity. When planning artificial reef deployment projects with heterotrophic reefs, managers should ensure ample water‐column space is provisioned to support them trophically.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Intersectionality in facilitators of active outdoor recreation in parks and protected areas - Sammie L. Powers; Julie S. Son; Hung-Ling (Stella) Liu; Nicole Webster (Journal of Outdoor Recreation and Tourism, 2025)

Remote sensing for species distribution models: An illustration from a sentinel taxon of the world's driest ecosystem - Khum B. Thapa‐Magar; Eric R. Sokol; Michael N. Gooseff; Mark R. Salvatore; John E. Barrett; Joseph S. Levy; Paul Knightly; Sarah N. Power (Ecology, 2025)
In situ observed data are commonly used as species occurrence response variables in species distribution models. However, the use of remotely observed data from high‐resolution multispectral remote‐sensing images as a source of presence/absence data for species distribution models remains under‐developed. Here, we describe an ensemble species distribution model of black microbial mats ( Nostoc spp.) using presence/absence points derived from the unmixing of 4‐m resolution WorldView‐2 and WorldView‐3 images in the Lake Fryxell basin region of Taylor Valley, Antarctica. Environmental and topographical characteristics such as soil moisture, snow, elevation, slope, and aspect were used as predictor variables in our models. We demonstrate that we can build and run ensemble species distribution models using both dependent and independent variables derived from remote‐sensing data to generate spatially explicit habitat suitability maps. Snow and soil moisture were found to be the most important variables accounting for about 80% of the variation in the distribution of black mats throughout the Fryxell basin. This study highlights the potential contribution of high‐resolution remote‐sensing to species distribution modeling and informs new studies incorporating remotely derived species occurrences in species distribution models, especially in remote areas where access to in situ data is often limited.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

From field station to forecast: managing data at the Alaska Volcano Observatory - Michelle L. Coombs; Cheryl E. Cameron; Hannah R. Dietterich; Eleanor S. Boyce; Aaron G. Wech; Ronni Grapenthin; Kristi L. Wallace; Tom Parker; Taryn Lopez; Scott Crass; David Fee; Matthew M. Haney; et al. (Bulletin of Volcanology, 2024)

Potential landscape connectivity for invasive wild pigs (Sus scrofa) across the northern prairies of North America - Corey J. Kramer; Melanie R. Boudreau; Ryan Powers; Kurt C. VerCauteren; Ryan S. Miller; Ryan K. Brook (Biological Invasions, 2024)

Southern Flounder: Major Milestones and Remaining Knowledge Gaps in Their Biology, Ecology, and Fishery Management - Stephen R. Midway; Frederick S. Scharf; Michael A. Dance; Nancy J. Brown-Peterson; Joseph C. Ballenger; Nicolette S. Beeken; Russell J. Borski; Tanya L. Darden; Kenneth A. Erickson; Troy M. Farmer; Ashley Fincannon; John Godwin; et al. (Reviews in Fisheries Science & Aquaculture, 2024)

Parents Report Positive Changes in Parental Feeding Practices 12 Months After Intervention - Theresa VB. Peirce; M. Catalina Aragón; Garry Auld; Karen V. Barale; Sheryl O. Hughes; Thomas G. Power; Jane D. Lanigan; Louise Parker; Susan S. Baker (Journal of Nutrition Education and Behavior, 2024)

Tropical root responses to global changes: A synthesis - Daniela Yaffar; Laynara F. Lugli; Michelle Y. Wong; Richard J. Norby; Shalom D. Addo‐Danso; Marie Arnaud; Amanda L. Cordeiro; Lee H. Dietterich; Milton H. Diaz‐Toribio; Ming Y. Lee; Om Prakash Ghimire; Chris M. Smith‐Martin; et al. (Global Change Biology, 2024)
Tropical ecosystems face escalating global change. These shifts can disrupt tropical forests' carbon (C) balance and impact root dynamics. Since roots perform essential functions such as resource acquisition and tissue protection, root responses can inform about the strategies and vulnerabilities of ecosystems facing present and future global changes. However, root trait dynamics are poorly understood, especially in tropical ecosystems. We analyzed existing research on tropical root responses to key global change drivers: warming, drought, flooding, cyclones, nitrogen (N) deposition, elevated (e) CO 2 , and fires. Based on tree species‐ and community‐level literature, we obtained 266 root trait observations from 93 studies across 24 tropical countries. We found differences in the proportion of root responsiveness to global change among different global change drivers but not among root categories. In particular, we observed that tropical root systems responded to warming and eCO 2 by increasing root biomass in species‐scale studies. Drought increased the root: shoot ratio with no change in root biomass, indicating a decline in aboveground biomass. Despite N deposition being the most studied global change driver, it had some of the most variable effects on root characteristics, with few predictable responses. Episodic disturbances such as cyclones, fires, and flooding consistently resulted in a change in root trait expressions, with cyclones and fires increasing root production, potentially due to shifts in plant community and nutrient inputs, while flooding changed plant regulatory metabolisms due to low oxygen conditions. The data available to date clearly show that tropical forest root characteristics and dynamics are responding to global change, although in ways that are not always predictable. This synthesis indicates the need for replicated studies across root characteristics at species and community scales under different global change factors.

Effects of lianas on forest biogeochemistry during their lives and afterlives - Gbadamassi G. O. Dossa; Hong‐Lin Li; Bo Pan; Tial C. Ling; Douglas A. Schaefer; Mareike Roeder; Denis M. Njoroge; Juan Zuo; Liang Song; Bismark Ofosu‐Bamfo; Stefan A. Schnitzer; Rhett D. Harrison; et al. (Global Change Biology, 2024)
Climate change and other anthropogenic disturbances are increasing liana abundance and biomass in many tropical and subtropical forests. While the effects of living lianas on species diversity, ecosystem carbon, and nutrient dynamics are receiving increasing attention, the role of dead lianas in forest ecosystems has been little studied and is poorly understood. Trees and lianas coexist as the major woody components of forests worldwide, but they have very different ecological strategies, with lianas relying on trees for mechanical support. Consequently, trees and lianas have evolved highly divergent stem, leaf, and root traits. Here we show that this trait divergence is likely to persist after death, into the afterlives of these organs, leading to divergent effects on forest biogeochemistry. We introduce a conceptual framework combining horizontal, vertical, and time dimensions for the effects of liana proliferation and liana tissue decomposition on ecosystem carbon and nutrient cycling. We propose a series of empirical studies comparing traits between lianas and trees to answer questions concerning the influence of trait afterlives on the decomposability of liana and tree organs. Such studies will increase our understanding of the contribution of lianas to terrestrial biogeochemical cycling, and help predict the effects of their increasing abundance.

A randomized placebo-controlled trial of nicotinamide riboside in older adults with mild cognitive impairment - Miranda E. Orr; Eithan Kotkowski; Paulino Ramirez; Darcy Bair-Kelps; Qianqian Liu; Charles Brenner; Mark S. Schmidt; Peter T. Fox; Anis Larbi; Crystal Tan; Glenn Wong; Jonathan Gelfond; et al. (GeroScience, 2023)

Evolving etiologies, comorbidities, survival, and costs of care in adult encephalitis - J. A. Bakal; R. Rivera; C. Charlton; S. Plitt; C. Power (Journal of NeuroVirology, 2023)

An improved method for computing tidal datums - Karen Palmer; Christopher S. Watson; John R. Hunter; Ben S. Hague; Hannah E. Power (Coastal Engineering, 2023)

The Western Lake Erie culture collection: A promising resource for evaluating the physiological and genetic diversity of Microcystis and its associated microbiome - Colleen E. Yancey; E. Anders Kiledal; Subba Rao Chaganti; Vincent J. Denef; Reagan M. Errera; Jacob T. Evans; Lauren N. Hart; Dragan Isailovic; William S. James; Jenan J. Kharbush; Jeffrey A. Kimbrel; Wei Li; et al. (Harmful Algae, 2023)

Drivers of the microbial metabolic quotient across global grasslands - A. C. Risch; S. Zimmermann; M. Schütz; E. T. Borer; A. A. D. Broadbent; M. C. Caldeira; K. F. Davies; N. Eisenhauer; A. Eskelinen; P. A. Fay; F. Hagedorn; J. M. H. Knops; et al. (Global Ecology and Biogeography, 2023)
Aim The microbial metabolic quotient (MMQ; mg CO 2 ‐C/mg MBC/h), defined as the amount of microbial CO 2 respired (MR; mg CO 2 ‐C/kg soil/h) per unit of microbial biomass C (MBC; mg C/kg soil), is a key parameter for understanding the microbial regulation of the carbon (C) cycle, including soil C sequestration. Here, we experimentally tested hypotheses about the individual and interactive effects of multiple nutrient addition (nitrogen + phosphorus + potassium + micronutrients) and herbivore exclusion on MR, MBC and MMQ across 23 sites (five continents). Our sites encompassed a wide range of edaphoclimatic conditions; thus, we assessed which edaphoclimatic variables affected MMQ the most and how they interacted with our treatments. Location Australia, Asia, Europe, North/South America. Time period 2015–2016. Major taxa Soil microbes. Methods Soils were collected from plots with established experimental treatments. MR was assessed in a 5‐week laboratory incubation without glucose addition, MBC via substrate‐induced respiration. MMQ was calculated as MR/MBC and corrected for soil temperatures (MMQsoil). Using linear mixed effects models (LMMs) and structural equation models (SEMs), we analysed how edaphoclimatic characteristics and treatments interactively affected MMQsoil. Results MMQsoil was higher in locations with higher mean annual temperature, lower water holding capacity and lower soil organic C concentration, but did not respond to our treatments across sites as neither MR nor MBC changed. We attributed this relative homeostasis to our treatments to the modulating influence of edaphoclimatic variables. For example, herbivore exclusion, regardless of fertilization, led to greater MMQsoil only at sites with lower soil organic C ( Main conclusions Our results pinpoint the main variables related to MMQsoil across grasslands and emphasize the importance of the local edaphoclimatic conditions in controlling the response of the C cycle to anthropogenic stressors. By testing hypotheses about MMQsoil across global edaphoclimatic gradients, this work also helps to align the conflicting results of prior studies.

121 Impact of environmental conditions and dragging schedules on changes in moisture content in equine arena footing - S. McGill; M. Hayes; K. Power; M. Peterson; R. Coleman (Journal of Equine Veterinary Science, 2023)

120 Determining moisture content in equine arena footing on-farm - S. McGill; M. Hayes; K. Power; M. Peterson; R. Coleman (Journal of Equine Veterinary Science, 2023)

Eccentric exercise-induced muscle weakness amplifies the history dependence of force - Vincenzo S. Contento; Geoffrey A. Power (European Journal of Applied Physiology, 2023)

Diel patterns of depth use and swimming activity of post-release greater amberjack (Seriola dumerili) in the northern Gulf of Mexico - Kelly S. Boyle; Crystal L. Hightower; Sean P. Powers (Environmental Biology of Fishes, 2023)

The impacts of a global pandemic on the efficacy and stability of contemporary wildlife conservation: South Africa as a case study - David A. Ehlers Smith; Yvette C. Ehlers Smith; Harriet T. Davies-Mostert; Lindy J. Thompson; Daniel M. Parker; Deon de Villiers; Dean Ricketts; Brent Coverdale; Peter J. Roberts; Christopher Kelly; Duncan N. Macfadyen; Nomthandazo S. Manqele; et al. (Ambio, 2023)
Conservationists speculated on potential benefits to wildlife of lockdown restrictions because of the COVID-19 pandemic but voiced concern that restrictions impeded nature conservation. We assessed the effects of lockdown restrictions on biodiversity conservation in South Africa, a biodiverse country with economic inequality and reliance on wildlife resources. We solicited expert opinion using the IUCN’s Threats Classification Scheme to structure a questionnaire and illustrated responses with individual case studies from government parastatal and non-governmental conservation organisations. The most highly reported threats were biological resource use, residential/commercial developments, invasive species, and human intrusions. The trends reported by 90 survey respondents were supported by case studies using environmental compliance data from parastatal conservation organisations. Lack of tourism revenue and funding were cited as hindrances to conservation. Mechanisms to prevent environmental degradation in the face of global emergencies must be implemented and ‘ring-fenced’ to ensure conservation is not a casualty during future global crises.

More than an anthropogenic phenomenon: Antimicrobial resistance in ungulates from natural and agricultural environments - Lee J. Pinnell; Grace Kuiper; Kate L. Huebner; Enrique Doster; Jennifer K. Parker; Najla Alekozai; Jenny G. Powers; Rick L. Wallen; Keith E. Belk; Paul S. Morley (Science of The Total Environment, 2023)

Climate processes and drivers in the Pacific and global warming: a review for informing Pacific planning agencies - Savin Chand; Scott Power; Kevin Walsh; Neil Holbrook; Kathleen McInnes; Kevin Tory; Hamish Ramsay; Ron Hoeke; Anthony S. Kiem (Climatic Change, 2023)
Pacific Island countries are vulnerable to climate variability and change. Developing strategies for adaptation and planning processes in the Pacific requires new knowledge and updated information on climate science. In this paper, we review key climatic processes and drivers that operate in the Pacific, how they may change in the future and what the impact of these changes might be. In particular, our emphasis is on the two major atmospheric circulation patterns, namely the Hadley and Walker circulations. We also examine climatic features such as the South Pacific Convergence Zone and Intertropical Convergence Zone, as well as factors that modulate natural climate variability on different timescales. It is anticipated that our review of the main climate processes and drivers that operate in the Pacific, as well as how these processes and drivers are likely to change in the future under anthropogenic global warming, can help relevant national agencies (such as Meteorological Services and National Disaster Management Offices) clearly communicate new information to sector-specific stakeholders and the wider community through awareness raising.

Long-term N-addition alters the community structure of functionally important N-cycling soil microorganisms across global grasslands - Beat Frey; Barbara Moser; Bjorn Tytgat; Stephan Zimmermann; Juan Alberti; Lori A. Biederman; Elizabeth T. Borer; Arthur A.D. Broadbent; Maria C. Caldeira; Kendi F. Davies; Nico Eisenhauer; Anu Eskelinen; et al. (Soil Biology and Biochemistry, 2023)

Uptake of microplastics by marine worms depends on feeding mode and particle shape but not exposure time - Adam Porter; Dan Barber; Catherine Hobbs; John Love; Ann L. Power; Adil Bakir; Tamara S. Galloway; Ceri Lewis (Science of The Total Environment, 2023)

Hyperspectral imaging predicts yield and nitrogen content in grass–legume polycultures - K. R. Ball; H. Liu; C. Brien; B. Berger; S. A. Power; E. Pendall (Precision Agriculture, 2022)

Leaf habit affects the distribution of drought sensitivity but not water transport efficiency in the tropics - German Vargas G.; Norbert Kunert; William M. Hammond; Z. Carter Berry; Leland K. Werden; Chris M. Smith‐Martin; Brett T. Wolfe; Laura Toro; Ariadna Mondragón‐Botero; Jesús N. Pinto‐Ledezma; Naomi B. Schwartz; María Uriarte; et al. (Ecology Letters, 2022)
Considering the global intensification of aridity in tropical biomes due to climate change, we need to understand what shapes the distribution of drought sensitivity in tropical plants. We conducted a pantropical data synthesis representing 1117 species to test whether xylem‐specific hydraulic conductivity (K S ), water potential at leaf turgor loss (Ψ TLP ) and water potential at 50% loss of K S (Ψ P50 ) varied along climate gradients. The Ψ TLP and Ψ P50 increased with climatic moisture only for evergreen species, but K S did not. Species with high Ψ TLP and Ψ P50 values were associated with both dry and wet environments. However, drought‐deciduous species showed high Ψ TLP and Ψ P50 values regardless of water availability, whereas evergreen species only in wet environments. All three traits showed a weak phylogenetic signal and a short half‐life. These results suggest strong environmental controls on trait variance, which in turn is modulated by leaf habit along climatic moisture gradients in the tropics.

Linking changes in species composition and biomass in a globally distributed grassland experiment - Emma Ladouceur; Shane A. Blowes; Jonathan M. Chase; Adam T. Clark; Magda Garbowski; Juan Alberti; Carlos Alberto Arnillas; Jonathan D. Bakker; Isabel C. Barrio; Siddharth Bharath; Elizabeth T. Borer; Lars A. Brudvig; et al. (Ecology Letters, 2022)
Global change drivers, such as anthropogenic nutrient inputs, are increasing globally. Nutrient deposition simultaneously alters plant biodiversity, species composition and ecosystem processes like aboveground biomass production. These changes are underpinned by species extinction, colonisation and shifting relative abundance. Here, we use the Price equation to quantify and link the contributions of species that are lost, gained or that persist to change in aboveground biomass in 59 experimental grassland sites. Under ambient (control) conditions, compositional and biomass turnover was high, and losses (i.e. local extinctions) were balanced by gains (i.e. colonisation). Under fertilisation, the decline in species richness resulted from increased species loss and decreases in species gained. Biomass increase under fertilisation resulted mostly from species that persist and to a lesser extent from species gained. Drivers of ecological change can interact relatively independently with diversity, composition and ecosystem processes and functions such as aboveground biomass due to the individual contributions of species lost, gained or persisting.

Age, growth and diet of crevalle jack ( Caranx hippos ) in the Gulf of Mexico - Amanda E. Jefferson; Matthew B. Jargowsky; Genevieve M. Ivec; Pearce T. Cooper; Jessica L. Carroll; Carissa L. Gervasi; Jennifer S. Rehage; John F. Mareska; Sean P. Powers; J. Marcus Drymon (Fisheries Management and Ecology, 2022)
The goals of this study were to generate baseline population dynamics parameters for Gulf of Mexico crevalle jack Caranx hippos and examine the foraging habits of Mississippi and Alabama crevalle jack. Specimens were collected from Mississippi, Alabama and Florida, and age was estimated from sagittal otoliths. Stomachs from some specimens were retained for dietary analyses. Age classes spanned 0–20 years. Overall growth was best represented by the logistic growth model, whereas sex‐specific growth was best represented by a version of the von Bertalanffy growth function that allowed L ∞ to vary by sex while holding k and t 0 constant between sexes. Fishes were more important to crevalle jack diet than invertebrates, and diet varied among locations and years. These findings will address fundamental knowledge gaps to inform age‐based stock assessments for crevalle jack and ecosystem approaches to fisheries management in the Gulf of Mexico.

Diel, temporal, and spatial patterns of biotic soundscapes among Alabama artificial reefs in late spring and summer - Kelly S. Boyle; Crystal L. Hightower; T. Reid Nelson; Sean P. Powers (Frontiers in Marine Science, 2022)
Passive acoustic monitoring (PAM) in a variety of marine habitats has revealed distinct spatial and temporal variation of fish sounds that are predicted to vary in association with species composition and abundance, as well as diel and seasonal influences. Reefs in the Alabama Artificial Reef Zone (AARZ) in the northern Gulf of Mexico (nGOM) have an associated fish fauna composed of warm-temperate and tropical reef associated species. AARZ reefs are made of different structures (e.g. bridge rubble, concrete pyramids, etc.) and as a result, their fish species composition is predicted to vary. We used PAM to describe fish sounds on 18 shallow slope (20-33 m) AARZ reefs in 2017 and 2018. We detected calls from unknown sources, as well as sounds from leopard toadfish Opsanus pardus , cocoa damselfish Stegastes variabilis , and cusk-eels (Ophidiidae). We developed semi-automated screening methods to detect specific sound types and described diel and spatial patterns. Sound detection rates varied widely among reefs, but not by reef type. Number of sound types increased with species richness, but detection rates of specific sounds differed on reefs with similar species composition. Our results indicate that many frequently occurring sounds may not be associated with visually conspicuous fishes. Further research is needed to determine source species and associated behavior for common sounds in these habitats. Soundscape variability among nGOM artificial reefs may be a consideration for management, as biological sound can provide an acoustic cue for reef location by some larval and adult fish species.

Transmission of Klebsiella strains and plasmids within and between grey‐headed flying fox colonies - Ben Vezina; Louise M. Judd; Fiona K. McDougall; Wayne S. J. Boardman; Michelle L. Power; Jane Hawkey; Sylvain Brisse; Jonathan M. Monk; Kathryn E. Holt; Kelly L. Wyres (Environmental Microbiology, 2022)
Summary The grey‐headed flying fox ( Pteropus poliocephalus ) is an endemic Australian fruit bat, known to carry zoonotic pathogens. We recently showed they harbour bacterial pathogen Klebsiella pneumoniae and closely related species in the K . pneumoniae species complex ( Kp SC); however, the dynamics of Kp SC transmission and gene flow within flying fox colonies are poorly understood. High‐resolution genome comparisons of 39 Kp SC isolates from grey‐headed flying foxes identified five putative strain transmission clusters (four intra‐ and one inter‐colony). The instance of inter‐colony strain transmission of K . africana was found between two flying fox populations within flying distance, indicating either direct or indirect transmission through a common food/water source. All 11 plasmids identified within the Kp SC isolates showed 73% coverage (mean) and ≥95% identity to human‐associated Kp SC plasmids, indicating gene flow between human clinical and grey‐headed flying fox isolates. Along with strain transmission, inter‐species horizontal plasmid transmission between K . pneumoniae and Klebsiella africana was also identified within a flying fox colony. Finally, genome‐scale metabolic models were generated to predict and compare substrate usage to previously published Kp SC models, from human and environmental sources. These models indicated no distinction on the basis of metabolic capabilities. Instead, metabolic capabilities were consistent with population structure and ST/lineage.

Transcriptomic Down-Regulation of Immune System Components in Barrier and Hematopoietic Tissues after Lipopolysaccharide Injection in Antarctic Notothenia coriiceps - Cármen S. V. Sousa; Deborah M. Power; Pedro M. Guerreiro; Bruno Louro; Liangbiao Chen; Adelino V. M. Canário (Fishes, 2022)
The environmental conditions and isolation in the Antarctic have driven the evolution of a unique biodiversity at a macro to microorganism scale. Here, we investigated the possible adaptation of the teleost Nototheniacoriiceps immune system to the cold environment and unique microbial community of the Southern Ocean. The fish immune system was stimulated through an intraperitoneal injection of lipopolysaccharide (LPS 0111:B4 from E. coli) and the tissue transcriptomic response and plasma biochemistry were analyzed 7 days later and compared to a sham injected control. Gene transcription in the head-kidney, intestine and skin was significantly modified by LPS, although tissues showed different responsiveness, with the duodenum most modified and the skin the least modified. The most modified processes in head-kidney, duodenum and skin were related to cell metabolism (up-regulated) and the immune system (comprising 30% of differentially expressed genes). The immune processes identified were mostly down-regulated, particularly interleukins and pattern recognition receptors (PRRs), nucleotide-binding oligomerization domain-like receptors and mannose receptors, unlike the toll-like receptors response commonly described in other teleost fish. The modified transcriptional response was not mirrored by a modified systemic response, as the circulating levels of enzymes of innate immunity, lysozyme and antiproteases, were not significantly different from the untreated and sham control fish. In conclusion, while the N.coriiceps immune system shares many features with other teleosts there are also some specificities. Further studies should better characterize the PRRs and their role in Antarctic teleosts, as well as the importance of the LPS source and its consequences for immune activation in teleosts.

Strategies to acquire and use phosphorus in phosphorus-impoverished and fire-prone environments - Hans Lambers; Patrícia de Britto Costa; Gregory R. Cawthray; Matthew D. Denton; Patrick M. Finnegan; Patrick E. Hayes; Rafael S. Oliveira; Simon C. Power; Kosala Ranathunge; Qi Shen; Xiao Wang; Hongtao Zhong (Plant and Soil, 2022)
Background Unveiling the diversity of plant strategies to acquire and use phosphorus (P) is crucial to understand factors promoting their coexistence in hyperdiverse P-impoverished communities within fire-prone landscapes such as in cerrado (South America), fynbos (South Africa) and kwongan (Australia). Scope We explore the diversity of P-acquisition strategies, highlighting one that has received little attention: acquisition of P following fires that temporarily enrich soil with P. This strategy is expressed by fire ephemerals as well as fast-resprouting perennial shrubs. A plant’s leaf manganese concentration ([Mn]) provides significant clues on P-acquisition strategies. High leaf [Mn] indicates carboxylate-releasing P-acquisition strategies, but other exudates may play the same role as carboxylates in P acquisition. Intermediate leaf [Mn] suggests facilitation of P acquisition by P-mobilising neighbours, through release of carboxylates or functionally similar compounds. Very low leaf [Mn] indicates that carboxylates play no immediate role in P acquisition. Release of phosphatases also represents a P-mining strategy, mobilising organic P. Some species may express multiple strategies, depending on time since germination or since fire, or on position in the landscape. In severely P-impoverished landscapes, photosynthetic P-use efficiency converges among species. Efficient species exhibit rapid rates of photosynthesis at low leaf P concentrations. A high P-remobilisation efficiency from senescing organs is another way to use P efficiently, as is extended longevity of plant organs. Conclusions Many P-acquisition strategies coexist in P-impoverished landscapes, but P-use strategies tend to converge. Common strategies of which we know little are those expressed by ephemeral or perennial species that are the first to respond after a fire. We surmise that carboxylate-releasing P-mobilising strategies are far more widespread than envisaged so far, and likely expressed by species that accumulate metals, exemplified by Mn, metalloids, such as selenium, fluorine, in the form of fluoroacetate, or silicon. Some carboxylate-releasing strategies are likely important to consider when restoring sites in biodiverse regions as well as in cropping systems on P-impoverished or strongly P-sorbing soils, because some species may only be able to establish themselves next to neighbours that mobilise P.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Nutrients and herbivores impact grassland stability across spatial scales through different pathways - Qingqing Chen; Shaopeng Wang; Eric W. Seabloom; Andrew S. MacDougall; Elizabeth T. Borer; Jonathan D. Bakker; Ian Donohue; Johannes M. H. Knops; John W. Morgan; Oliver Carroll; Mick Crawley; Miguel N. Bugalho; et al. (Global Change Biology, 2022)
Nutrients and herbivores are well‐known drivers of grassland diversity and stability in local communities. However, whether they interact to impact the stability of aboveground biomass and whether these effects depend on spatial scales remain unknown. It is also unclear whether nutrients and herbivores impact stability via different facets of plant diversity including species richness, evenness, and changes in community composition through time and space. We used a replicated experiment adding nutrients and excluding herbivores for 5 years in 34 global grasslands to explore these questions. We found that both nutrient addition and herbivore exclusion alone reduced stability at the larger spatial scale (aggregated local communities; gamma stability), but through different pathways. Nutrient addition reduced gamma stability primarily by increasing changes in local community composition over time, which was mainly driven by species replacement. Herbivore exclusion reduced gamma stability primarily by decreasing asynchronous dynamics among local communities (spatial asynchrony). Their interaction weakly increased gamma stability by increasing spatial asynchrony. Our findings indicate that disentangling the processes operating at different spatial scales may improve conservation and management aiming at maintaining the ability of ecosystems to reliably provide functions and services for humanity.

Effects of short-term decomposition on isotope values of fish tissues under natural conditions - Kathryn S. Peiman; Hsien-Yung Lin; Michael Power; Scott G. Hinch; David A. Patterson; Steven J. Cooke (Aquatic Ecology, 2022)

Reduced ecosystem resilience quantifies fine‐scale heterogeneity in tropical forest mortality responses to drought - Donghai Wu; German Vargas G.; Jennifer S. Powers; Nate G. McDowell; Justin M. Becknell; Daniel Pérez‐Aviles; David Medvigy; Yanlan Liu; Gabriel G. Katul; Julio César Calvo‐Alvarado; Ana Calvo‐Obando; Arturo Sanchez‐Azofeifa; et al. (Global Change Biology, 2022)
Sensitivity of forest mortality to drought in carbon‐dense tropical forests remains fraught with uncertainty, while extreme droughts are predicted to be more frequent and intense. Here, the potential of temporal autocorrelation of high‐frequency variability in Landsat Enhanced Vegetation Index (EVI), an indicator of ecosystem resilience, to predict spatial and temporal variations of forest biomass mortality is evaluated against in situ census observations for 64 site‐year combinations in Costa Rican tropical dry forests during the 2015 ENSO drought. Temporal autocorrelation, within the optimal moving window of 24 months, demonstrated robust predictive power for in situ mortality (leave‐one‐out cross‐validation R 2 = 0.54), which allows for estimates of annual biomass mortality patterns at 30 m resolution. Subsequent spatial analysis showed substantial fine‐scale heterogeneity of forest mortality patterns, largely driven by drought intensity and ecosystem properties related to plant water use such as forest deciduousness and topography. Highly deciduous forest patches demonstrated much lower mortality sensitivity to drought stress than less deciduous forest patches after elevation was controlled. Our results highlight the potential of high‐resolution remote sensing to “fingerprint” forest mortality and the significant role of ecosystem heterogeneity in forest biomass resistance to drought.

The genetic and ecophysiological diversity of Microcystis - Gregory J. Dick; Melissa B. Duhaime; Jacob T. Evans; Reagan M. Errera; Casey M. Godwin; Jenan J. Kharbush; Helena S. Nitschky; McKenzie A. Powers; Henry A. Vanderploeg; Kathryn C. Schmidt; Derek J. Smith; Colleen E. Yancey; et al. (Environmental Microbiology, 2021)
Summary Microcystis is a cyanobacterium that forms toxic blooms in freshwater ecosystems around the world. Biological variation among taxa within the genus is apparent through genetic and phenotypic differences between strains and via the spatial and temporal distribution of strains in the environment, and this fine‐scale diversity exerts strong influence over bloom toxicity. Yet we do not know how varying traits of Microcystis strains govern their environmental distribution, the tradeoffs and links between these traits, or how they are encoded at the genomic level. Here we synthesize current knowledge on the importance of diversity within Microcystis and on the genes and traits that likely underpin ecological differentiation of taxa. We briefly review spatial and environmental patterns of Microcystis diversity in the field and genetic evidence for cohesive groups within Microcystis . We then compile data on strain‐level diversity regarding growth responses to environmental conditions and explore evidence for variation of community interactions across Microcystis strains. Potential links and tradeoffs between traits are identified and discussed. The resulting picture, while incomplete, highlights key knowledge gaps that need to be filled to enable new models for predicting strain‐level dynamics, which influence the development, toxicity and cosmopolitan nature of Microcystis blooms.

Early chemical changes during wood decomposition are controlled by fungal communities inhabiting stems at treefall in a tropical dry forest - François Maillard; Erin Andrews; Molly Moran; Dan V. Du; Peter G. Kennedy; Jennifer S. Powers; Skip J. Van Bloem; Jonathan S. Schilling (Plant and Soil, 2021)

Integrating Ecological Stoichiometry to Understand Nutrient Limitation and Potential for Competition in Mixed Pasture Assemblages - K. R. Ball; S. J. Woodin; S. A. Power; C. Brien; B. Berger; P. Smith; E. Pendall (Journal of Soil Science and Plant Nutrition, 2021)

Chronic resistance training: is it time to rethink the time course of neural contributions to strength gain? - G. E. P. Pearcey; S. Alizedah; K. E. Power; D. C. Button (European Journal of Applied Physiology, 2021)

Estimating and Applying Fish and Invertebrate Density and Production Enhancement from Seagrass, Salt Marsh Edge, and Oyster Reef Nursery Habitats in the Gulf of Mexico - Philine S. E. zu Ermgassen; Bryan DeAngelis; Jonathan R. Gair; Sophus zu Ermgassen; Ronald Baker; Andre Daniels; Timothy C. MacDonald; Kara Meckley; Sean Powers; Marta Ribera; Lawrence P. Rozas; Jonathan H. Grabowski (Estuaries and Coasts, 2021)
Seagrasses, oyster reefs, and salt marshes are critical coastal habitats that support high densities of juvenile fish and invertebrates. Yet which species are enhanced through these nursery habitats, and to what degree, remains largely unquantified. Densities of young-of-year fish and invertebrates in seagrasses, oyster reefs, and salt marsh edges as well as in paired adjacent unstructured habitats of the northern Gulf of Mexico were compiled. Species consistently found at higher densities in the structured habitats were identified, and species-specific growth and mortality models were applied to derive production enhancement estimates arising from this enhanced density. Enhancement levels for fish and invertebrate production were similar for seagrass (1370 [SD 317] g m –2 y –1 for 25 enhanced species) and salt marsh edge habitats (1222 [SD 190] g m –2 y –1 , 25 spp.), whereas oyster reefs produced ~650 [SD 114] g m –2 y –1 (20 spp). This difference was partly due to lower densities of juvenile blue crab ( Callinectes sapidus ) on oyster reefs, although only oyster reefs enhanced commercially valuable stone crabs ( Menippe spp.). The production estimates were applied to Galveston Bay, Texas, and Pensacola Bay, Florida, for species known to recruit consistently in those embayments. These case studies illustrated variability in production enhancement by coastal habitats within the northern Gulf of Mexico. Quantitative estimates of production enhancement within specific embayments can be used to quantify the role of essential fish habitat, inform management decisions, and communicate the value of habitat protection and restoration.

Progress on reducing acrylamide levels in potato crisps in Europe, 2002 to 2019 - Stephen J. Powers; Donald S. Mottram; Andrew Curtis; Nigel G. Halford (Food Additives & Contaminants: Part A, 2021)

The clinical presentation, treatment and outcome of serologically confirmed paediatric Lyme disease in the Republic of Ireland over a 5-year period: a retrospective cohort study - Karina M. Forde; Joanne O’Gorman; Patrick J. Gavin; Matthew S. Dryden; Deirbhile Keady; Belinda Hanahoe; Colm McDonnell; Lorraine Power; Bartley Cryan; James Sweeney; Karl F. Conyard; Michael J. O’Grady (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Diet overlap of common and at-risk riverine benthic fishes before and after Round Goby (Neogobius melanostomus) invasion - B. L. Firth; M. S. Poesch; M. A. Koops; D. A. R. Drake; M. Power (Biological Invasions, 2021)

The long and short of residual force enhancement non-responders - Geoffrey A. Power; Avery Hinks; Parastoo Mashouri; Vincenzo S. Contento; Jackey Chen (European Journal of Applied Physiology, 2020)

Global impacts of fertilization and herbivore removal on soil net nitrogen mineralization are modulated by local climate and soil properties - Anita C. Risch; Stefan Zimmermann; Barbara Moser; Martin Schütz; Frank Hagedorn; Jennifer Firn; Philip A. Fay; Peter B. Adler; Lori A. Biederman; John M. Blair; Elizabeth T. Borer; Arthur A. D. Broadbent; et al. (Global Change Biology, 2020)
Soil nitrogen (N) availability is critical for grassland functioning. However, human activities have increased the supply of biologically limiting nutrients, and changed the density and identity of mammalian herbivores. These anthropogenic changes may alter net soil N mineralization (soil net N min ), that is, the net balance between N mineralization and immobilization, which could severely impact grassland structure and functioning. Yet, to date, little is known about how fertilization and herbivore removal individually, or jointly, affect soil net N min across a wide range of grasslands that vary in soil and climatic properties. Here we collected data from 22 grasslands on five continents, all part of a globally replicated experiment, to assess how fertilization and herbivore removal affected potential (laboratory‐based) and realized (field‐based) soil net N min . Herbivore removal in the absence of fertilization did not alter potential and realized soil net N min . However, fertilization alone and in combination with herbivore removal consistently increased potential soil net N min. Realized soil net N min , in contrast, significantly decreased in fertilized plots where herbivores were removed. Treatment effects on potential and realized soil net N min were contingent on site‐specific soil and climatic properties. Fertilization effects on potential soil net N min were larger at sites with higher mean annual precipitation (MAP) and temperature of the wettest quarter (T.q.wet). Reciprocally, realized soil net N min declined most strongly with fertilization and herbivore removal at sites with lower MAP and higher T.q.wet. In summary, our findings show that anthropogenic nutrient enrichment, herbivore exclusion and alterations in future climatic conditions can negatively impact soil net N min across global grasslands under realistic field conditions. This is an important context‐dependent knowledge for grassland management worldwide.

Lianas maintain insectivorous bird abundance and diversity in a neotropical forest - Stefan A. Schnitzer; Nicole L. Michel; Jennifer S. Powers; W. Douglas Robinson (Ecology, 2020)
The spatial habitat heterogeneity hypothesis posits that habitat complexity increases the abundance and diversity of species. In tropical forests, lianas add substantial habitat heterogeneity and complexity throughout the vertical forest profile, which may maintain animal abundance and diversity. The effects of lianas on tropical animal communities, however, remain poorly understood. We propose that lianas have a positive effect on animals by enhancing habitat complexity. Lianas may have a particularly strong influence on the forest bird community, providing nesting substrate, protection from predators, and nutrition (food). Understory insectivorous birds, which forage for insects that specialize on lianas, may particularly benefit. Alternatively, it is possible that lianas have a negative effect on forest birds by increasing predator abundances and providing arboreal predators with travel routes with easy access to bird nests. We tested the spatial habitat heterogeneity hypothesis on bird abundance and diversity by removing lianas, thus reducing forest complexity, using a large‐scale experimental approach in a lowland tropical forest in the Republic of Panama. We found that removing lianas decreased total bird abundance by 78.4% and diversity by 77.4% after 8 months, and by 40.0% and 51.7%, respectively, after 20 months. Insectivorous bird abundance and diversity 8 months after liana removal were 91.8% and 89.5% lower, respectively, indicating that lianas positively influence insectivorous birds. The effects of liana removal persisted longer for insectivorous birds than other birds, with 77.3% lower abundance and 76.2% lower diversity after 20 months. Liana removal also altered bird community composition, creating two distinct communities in the control and removal plots, with disproportionate effects on insectivores. Our findings demonstrate that lianas have a strong positive influence on the bird community, particularly for insectivorous birds in the forest understory. Lianas may maintain bird abundance and diversity by increasing habitat complexity, habitat heterogeneity, and resource availability.

A Marine Biodiversity Observation Network for Genetic Monitoring of Hard-Bottom Communities (ARMS-MBON) - Matthias Obst; Katrina Exter; A. Louise Allcock; Christos Arvanitidis; Alizz Axberg; Maria Bustamante; Ibon Cancio; Diego Carreira-Flores; Eva Chatzinikolaou; Giorgos Chatzigeorgiou; Nathan Chrismas; Melody S. Clark; et al. (Frontiers in Marine Science, 2020)
Marine hard-bottom communities are undergoing severe change under the influence of multiple drivers, notably climate change, extraction of natural resources, pollution and eutrophication, habitat degradation, and invasive species. Monitoring marine biodiversity in such habitats is, however, challenging as it typically involves expensive, non-standardized, and often destructive sampling methods that limit its scalability. Differences in monitoring approaches furthermore hinders inter-comparison among monitoring programs. Here, we announce a Marine Biodiversity Observation Network (MBON) consisting of Autonomous Reef Monitoring Structures (ARMS) with the aim to assess the status and changes in benthic fauna with genomic-based methods, notably DNA metabarcoding, in combination with image-based identifications. This article presents the results of a 30-month pilot phase in which we established an operational and geographically expansive ARMS-MBON. The network currently consists of 20 observatories distributed across European coastal waters and the polar regions, in which 134 ARMS have been deployed to date. Sampling takes place annually, either as short-term deployments during the summer or as long-term deployments starting in spring. The pilot phase was used to establish a common set of standards for field sampling, genetic analysis, data management, and legal compliance, which are presented here. We also tested the potential of ARMS for combining genetic and image-based identification methods in comparative studies of benthic diversity, as well as for detecting non-indigenous species. Results show that ARMS are suitable for monitoring hard-bottom environments as they provide genetic data that can be continuously enriched, re-analyzed, and integrated with conventional data to document benthic community composition and detect non-indigenous species. Finally, we provide guidelines to expand the network and present a sustainability plan as part of the European Marine Biological Resource Centre ( www.embrc.eu ).

The association between job strain, depressive symptoms, and cardiovascular disease risk: results from a cross-sectional population-based study in Québec, Canada - Niamh Power; Sonya S. Deschênes; Floriana Ferri; Norbert Schmitz (International Archives of Occupational and Environmental Health, 2020)

Microbial processing of plant remains is co‐limited by multiple nutrients in global grasslands - Raúl Ochoa‐Hueso; Elizabeth T. Borer; Eric W. Seabloom; Sarah E. Hobbie; Anita C. Risch; Scott L. Collins; Juan Alberti; Héctor A. Bahamonde; Cynthia S. Brown; Maria C. Caldeira; Pedro Daleo; Chris R. Dickman; et al. (Global Change Biology, 2020)
Microbial processing of aggregate‐unprotected organic matter inputs is key for soil fertility, long‐term ecosystem carbon and nutrient sequestration and sustainable agriculture. We investigated the effects of adding multiple nutrients (nitrogen, phosphorus and potassium plus nine essential macro‐ and micro‐nutrients) on decomposition and biochemical transformation of standard plant materials buried in 21 grasslands from four continents. Addition of multiple nutrients weakly but consistently increased decomposition and biochemical transformation of plant remains during the peak‐season, concurrent with changes in microbial exoenzymatic activity. Higher mean annual precipitation and lower mean annual temperature were the main climatic drivers of higher decomposition rates, while biochemical transformation of plant remains was negatively related to temperature of the wettest quarter. Nutrients enhanced decomposition most at cool, high rainfall sites, indicating that in a warmer and drier future fertilized grassland soils will have an even more limited potential for microbial processing of plant remains.

A catastrophic tropical drought kills hydraulically vulnerable tree species - Jennifer S. Powers; German Vargas G.; Timothy J. Brodribb; Naomi B. Schwartz; Daniel Pérez‐Aviles; Chris M. Smith‐Martin; Justin M. Becknell; Filippo Aureli; Roger Blanco; Erick Calderón‐Morales; Julio C. Calvo‐Alvarado; Ana Julieta Calvo‐Obando; et al. (Global Change Biology, 2020)
Drought‐related tree mortality is now a widespread phenomenon predicted to increase in magnitude with climate change. However, the patterns of which species and trees are most vulnerable to drought, and the underlying mechanisms have remained elusive, in part due to the lack of relevant data and difficulty of predicting the location of catastrophic drought years in advance. We used long‐term demographic records and extensive databases of functional traits and distribution patterns to understand the responses of 20–53 species to an extreme drought in a seasonally dry tropical forest in Costa Rica, which occurred during the 2015 El Niño Southern Oscillation event. Overall, species‐specific mortality rates during the drought ranged from 0% to 34%, and varied little as a function of tree size. By contrast, hydraulic safety margins correlated well with probability of mortality among species, while morphological or leaf economics spectrum traits did not. This firmly suggests hydraulic traits as targets for future research.

Effect of Shallow Slip Amplification Uncertainty on Probabilistic Tsunami Hazard Analysis in Subduction Zones: Use of Long-Term Balanced Stochastic Slip Models - A. Scala; S. Lorito; F. Romano; S. Murphy; J. Selva; R. Basili; A. Babeyko; A. Herrero; A. Hoechner; F. Løvholt; F. E. Maesano; P. Perfetti; et al. (Pure and Applied Geophysics, 2020)

Defining Sex-Specific Habitat Suitability for a Northern Gulf of Mexico Shark Assemblage - J. M. Drymon; S. Dedman; J. T. Froeschke; E. A. Seubert; A. E. Jefferson; A. M. Kroetz; J. F. Mareska; S. P. Powers (Frontiers in Marine Science, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Transcutaneous electrical nerve stimulation improves fatigue performance of the treated and contralateral knee extensors - D. G. Behm; E. M. Colwell; G. M. J. Power; H. Ahmadi; A. S. M. Behm; A. Bishop; C. Murph; J. Pike; B. McAssey; K. Fraser; S. Kearley; M. Ryan (European Journal of Applied Physiology, 2019)

Assessing Nearshore Nekton Abundance, Substrate, and Environmental Conditions in the Northern Gulf of Mexico: Are There Differences Among Three Adjacent Coastal Areas and Have There Been Changes over Three Decades (1986–2015)? - Martin T. O’Connell; Mark S. Peterson; Sean P. Powers; Ann M. Uzee-O’Connell; E. John Anderson; J. Read Hendon (Estuaries and Coasts, 2019)

3D seismic-derived bathymetry: a quantitative comparison with multibeam data - H. E. Power; S. L. Clarke (Geo-Marine Letters, 2019)

Effects of dry‐season irrigation on leaf physiology and biomass allocation in tropical lianas and trees - Chris M. Smith‐Martin; Carolina L. Bastos; Omar R. Lopez; Jennifer S. Powers; Stefan A. Schnitzer (Ecology, 2019)
Lianas are more abundant in seasonal forests than in wetter forests and are thought to perform better than trees when light is abundant and water is limited. We tested the hypothesis that lianas perform better than trees during seasonal drought using a common garden experiment with 12 taxonomically diverse species (six liana and six tree species) in 12 replicated plots. We irrigated six of the plots during the dry season for four years, while the remaining six control plots received only ambient rainfall. In year 5, we measured stem diameters for all individuals and harvested above‐ and belowground biomass for a subset of individuals to quantify absolute growth and biomass allocation to roots, stems, and leaves, as well as total root length and maximum rooting depth. We also measured rate of photosynthesis, intrinsic water use efficiency ( iWUE ), pre‐dawn and midday water potential, and a set of functional and hydraulic traits. During the peak of the dry season, lianas in control plots had 54% higher predawn leaf water potentials (Ψ PD ), and 45% higher photosynthetic rates than trees in control plots. By contrast, during the peak of the wet season, these physiological differences between lianas and trees become less pronounced and, in some cases, even disappeared. Trees had higher specific leaf area ( SLA ) than lianas; however, no other functional trait differed between growth forms. Trees responded to the irrigation treatment with 15% larger diameters and 119% greater biomass than trees in control plots. Liana growth, however, did not respond to irrigation; liana diameter and biomass were similar in control and irrigation plots, suggesting that lianas were far less limited by soil moisture than were trees. Contrary to previous hypotheses, lianas did not have deeper roots than trees; however, lianas had longer roots per stem diameter than did trees. Our results support the hypothesis that lianas perform better and experience less physiological stress than trees during seasonal drought, suggesting clear differences between growth forms in response to altered rainfall regimes. Ultimately, better dry‐season performance may explain why liana abundance peaks in seasonal forests compared to trees, which peak in abundance in less seasonal, wetter forests.

Tiger sharks eat songbirds: reply - J. M. Drymon; K. Feldheim; A. M. V. Fournier; E. A. Seubert; A. E. Jefferson; A. M. Kroetz; S. P. Powers (Ecology, 2019)

A framework to measure the wildness of managed large vertebrate populations - Matthew F. Child; S. A. Jeanetta Selier; Frans G. T. Radloff; W. Andrew Taylor; Michael Hoffmann; Lizanne Nel; R. John Power; Coral Birss; Nicola C. Okes; Michael J. Peel; David Mallon; Harriet Davies‐Mostert (Conservation Biology, 2019)
As landscapes continue to fall under human influence through habitat loss and fragmentation, fencing is increasingly being used to mitigate anthropogenic threats and enhance the commercial value of wildlife. Subsequent intensification of management potentially erodes wildness by disembodying populations from landscape‐level processes, thereby disconnecting species from natural selection. Tools are needed to measure the degree to which populations of large vertebrate species in formally protected and privately owned wildlife areas are self‐sustaining and free to adapt. We devised a framework to measure such wildness based on 6 attributes relating to the evolutionary and ecological dynamics of vertebrates (space, disease and parasite resistance, exposure to predation, exposure to limitations and fluctuations of food and water supply, and reproduction). For each attribute, we set empirical, species‐specific thresholds between 5 wildness states based on quantifiable management interventions. We analysed data from 205 private wildlife properties with management objectives spanning ecotourism to consumptive utilization to test the framework on 6 herbivore species representing a range of conservation statuses and commercial values. Wildness scores among species differed significantly, and the proportion of populations identified as wild ranged from 12% to 84%, which indicates the tool detected site‐scale differences both among populations of different species and populations of the same species under different management regimes. By quantifying wildness, this framework provides practitioners with standardized measurement units that link biodiversity with the sustainable use of wildlife. Applications include informing species management plans at local scales; standardizing the inclusion of managed populations in red‐list assessments; and providing a platform for certification and regulation of wildlife‐based economies. Applying this framework may help embed wildness as a normative value in policy and mitigate the shifting baseline of what it means to truly conserve a species.

Tiger sharks eat songbirds: scavenging a windfall of nutrients from the sky - J. M. Drymon; K. Feldheim; A. M. V. Fournier; E. A. Seubert; A. E. Jefferson; A. M. Kroetz; S. P. Powers (Ecology, 2019)

Plant community responses to stand‐level nutrient fertilization in a secondary tropical dry forest - Bonnie G. Waring; Daniel Pérez‐Aviles; Jessica G. Murray; Jennifer S. Powers (Ecology, 2019)
The size of the terrestrial carbon (C) sink is mediated by the availability of nutrients that limit plant growth. However, nutrient controls on primary productivity are poorly understood in the geographically extensive yet understudied tropical dry forest biome. To examine how nutrients influence above‐ and belowground biomass production in a secondary, seasonally dry tropical forest, we conducted a replicated, fully factorial nitrogen (N) and phosphorus (P) fertilization experiment at the stand scale in Guanacaste, Costa Rica. The production of leaves, wood, and fine roots was monitored through time; root colonization by mycorrhizal fungi and the abundance of N‐fixing root nodules were also quantified. In this seasonal forest, interannual variation in rainfall had the largest influence on stand‐level productivity, with lower biomass growth under drought. By contrast, aboveground productivity was generally not increased by nutrient addition, although fertilization enhanced growth of individual tree stems in a wet year. However, root growth increased markedly and consistently under P addition, significantly altering patterns of stand‐level biomass allocation to above‐ vs. belowground compartments. Although nutrients did not stimulate total biomass production at the community scale, N‐fixing legumes exhibited a twofold increase in woody growth in response to added P, accompanied by a dramatic increase in the abundance of root nodules. These data suggest that the relationship between nutrient availability and primary production in tropical dry forest is contingent on both water availability and plant functional diversity.

Whole Genome Sequence Analysis of Burkholderia contaminans FFH2055 Strain Reveals the Presence of Putative β-Lactamases - José J. Degrossi; Cindy Merino; Adela M. Isasmendi; Lorena M. Ibarra; Chelsea Collins; Nicolás E. Bo; Mariana Papalia; Jennifer S. Fernandez; Claudia M. Hernandez; Krisztina M. Papp-Wallace; Robert A. Bonomo; Miryam S. Vazquez; et al. (Current Microbiology, 2019)

Social-ecological research in urban natural areas: an emergent process for integration - Michelle L. Johnson; D. S. Novem Auyeung; Nancy F. Sonti; Clara C. Pregitzer; Heather L. McMillen; Richard Hallett; Lindsay K. Campbell; Helen M. Forgione; Mina Kim; Sarah Charlop-Powers; Erika S. Svendsen (Urban Ecosystems, 2019)

Central contributions to torque depression: an antagonist perspective - Caleb T. Sypkes; Vincenzo S. Contento; Leah R. Bent; Chris J. McNeil; Geoffrey A. Power (Experimental Brain Research, 2019)

Bonefish in South Florida: status, threats and research needs - Jacob W. Brownscombe; Andy J. Danylchuk; Aaron J. Adams; Brooke Black; Ross Boucek; Michael Power; Jennifer S. Rehage; Rolando O. Santos; Russ W. Fisher; Bill Horn; Christopher R. Haak; Sean Morton; et al. (Environmental Biology of Fishes, 2019)

Diverse effects of the common hippopotamus on plant communities and soil chemistry - Douglas J. McCauley; Stuart I. Graham; Todd E. Dawson; Mary E. Power; Mordecai Ogada; Wanja D. Nyingi; John M. Githaiga; Judith Nyunja; Lacey F. Hughey; Justin S. Brashares (Oecologia, 2018)

Resilience of seed production to a severe El Niño‐induced drought across functional groups and dispersal types - Michael J. O'Brien; Daniel Peréz‐Aviles; Jennifer S. Powers (Global Change Biology, 2018)
More frequent and severe El Niño Southern Oscillations (ENSO) are causing episodic periods of decreased rainfall. Although the effects of these ENSO‐induced droughts on tree growth and mortality have been well studied, the impacts on other demographic rates such as reproduction are less well known. We use a four‐year seed rain dataset encompassing the most severe ENSO‐induced drought in more than 30 years to assess the resilience (i.e., resistance and recovery) of the seed composition and abundance of three forest types in a tropical dry forest. We found that forest types showed distinct differences in the timing, duration, and intensity of drought during the ENSO event, which likely mediated seed composition shifts and resilience. Drought‐deciduous species were particularly sensitive to the drought with overall poor resilience of seed production, whereby seed abundance of this functional group failed to recover to predrought levels even two years after the drought. Liana and wind‐dispersed species were able to maintain seed production both during and after drought, suggesting that ENSO events promote early successional species or species with a colonization strategy. Combined, these results suggest that ENSO‐induced drought mediates the establishment of functional groups and dispersal types suited for early successional conditions with more open canopies and reduced competition among plants. The effects of the ENSO‐induced drought on seed composition and abundance were still evident two years after the event suggesting the recovery of seed production requires multiple years that may lead to shifts in forest composition and structure in the long term, with potential consequences for higher trophic levels like frugivores.

Calcium mishandling impairs contraction in right ventricular hypertrophy prior to overt heart failure - Amelia S. Power; Anthony J. Hickey; David J. Crossman; Denis S. Loiselle; Marie-Louise Ward (Pflügers Archiv - European Journal of Physiology, 2018)

Effects of competition and herbivory over woody seedling growth in a temperate woodland trump the effects of elevated CO2 - L. Collins; M. M. Boer; V. Resco de Dios; S. A. Power; E. R. Bendall; S. Hasegawa; R. Ochoa Hueso; J. Piñeiro Nevado; R. A. Bradstock (Oecologia, 2018)

What shapes plant and animal diversity on urban golf courses? - Sabine S. Nooten; Patrick Schultheiss; Jules Wright; Catriona Macdonald; Brajesh K. Singh; James M. Cook; Sally A. Power (Urban Ecosystems, 2018)

Socio-environmental consideration of phosphorus flows in the urban sanitation chain of contrasting cities - Geneviève S. Metson; Steve M. Powers; Rebecca L. Hale; Jesse S. Sayles; Gunilla Öberg; Graham K. MacDonald; Yusuke Kuwayama; Nathaniel P. Springer; Anthony J. Weatherley; Kelly L. Hondula; Kristal Jones; Rubel B. Chowdhury; et al. (Regional Environmental Change, 2018)

Structural and functional maturation of skin during metamorphosis in the Atlantic halibut (Hippoglossus hippoglossus) - Ricardo N. Alves; Kristina S. Sundell; Liliana Anjos; Henrik Sundh; Torstein Harboe; Birgitta Norberg; Deborah M. Power (Cell and Tissue Research, 2018)

A comparison of the trophic ecology of Beaufort Sea Gadidae using fatty acids and stable isotopes - J. D. Brewster; C. Giraldo; E. S. Choy; S. A. MacPhee; C. Hoover; B. Lynn; D. G. McNicholl; A. Majewski; B. Rosenberg; M. Power; J. D. Reist; L. L. Loseto (Polar Biology, 2018)

Acrylamide levels in potato crisps in Europe from 2002 to 2016 - Stephen J. Powers; Donald S. Mottram; Andrew Curtis; Nigel G. Halford (Food Additives & Contaminants: Part A, 2017)

Daily temperature experience and selection by adfluvial bull trout (Salvelinus confluentus) - L. F. G. Gutowsky; P. M. Harrison; E. G. Martins; A. Leake; D. A. Patterson; D. Z. Zhu; M. Power; S. J. Cooke (Environmental Biology of Fishes, 2017)

Thermal pasteurization of ready-to-eat foods and vegetables: Critical factors for process design and effects on quality - Jing Peng; Juming Tang; Diane M. Barrett; Shyam S. Sablani; Nathan Anderson; Joseph R. Powers (Critical Reviews in Food Science and Nutrition, 2017)

Modeling brain lentiviral infections during antiretroviral therapy in AIDS - Weston C. Roda; Michael Y. Li; Michael S. Akinwumi; Eugene L. Asahchop; Benjamin B. Gelman; Kenneth W. Witwer; Christopher Power (Journal of NeuroVirology, 2017)

DIMBOA levels in hexaploid Brazilian wheat are not associated with antibiosis against the cereal aphids Rhopalosiphum padi and Sitobion avenae - Jorge F. Pereira; André L. F. Sarria; Stephen J. Powers; Gudbjorg I. Aradottir; John C. Caulfield; Janet Martin; Lesley E. Smart; John A. Pickett; Michael A. Birkett; Paulo R. V. S. Pereira (Theoretical and Experimental Plant Physiology, 2017)

Individual isotopic specializations predict subsequent inter‐individual variation in movement in a freshwater fish - P. M. Harrison; L. F. G. Gutowsky; E. G. Martins; T. D. Ward; D. A. Patterson; S. J. Cooke; M. Power (Ecology, 2017)
Despite many similarities and intuitive links between individual dietary specialization and behavioral inter‐individual variation, these phenomena have been studied in isolation, and empirical data confirming relationships between these intraspecific variance sources are lacking. Here we use stable isotope analysis and acoustic telemetry to test the hypothesis that individual specialization in trophic (δ 15 N) and littoral/pelagic prey reliance (δ 13 C) covary with inter‐individual variation in movement in a group of 34 free‐swimming burbot ( Lota lota ). By performing stable isotope analysis on tissues with differing isotopic turnover rates (anal fin and dorsal muscle), in 24 lethally sampled burbot, we demonstrate that individual specialization in trophic niche (δ 15 N) and littoral/pelagic prey reliance (δ 13 C) occurred within the population. By performing stable isotope analysis on anal fins of a group of telemetry tagged burbot, we were able to show that interactions between trophic niche and littoral/pelagic prey reliance, explained a significant proportion of the subsequent between‐individual variance in mean movement rates. These findings demonstrate an empirical connection between behavioral inter‐individual variation and dietary specialization, thus providing a substantial expansion of our understanding of the wider ecological consequences of these interesting phenomena.

cis-Jasmone Elicits Aphid-Induced Stress Signalling in Potatoes - Islam S. Sobhy; Christine M. Woodcock; Stephen J. Powers; John C. Caulfield; John A. Pickett; Michael A. Birkett (Journal of Chemical Ecology, 2017)

Ecology under lake ice - Stephanie E. Hampton; Aaron W. E. Galloway; Stephen M. Powers; Ted Ozersky; Kara H. Woo; Ryan D. Batt; Stephanie G. Labou; Catherine M. O'Reilly; Sapna Sharma; Noah R. Lottig; Emily H. Stanley; Rebecca L. North; et al. (Ecology Letters, 2017)
Winter conditions are rapidly changing in temperate ecosystems, particularly for those that experience periods of snow and ice cover. Relatively little is known of winter ecology in these systems, due to a historical research focus on summer ‘growing seasons’. We executed the first global quantitative synthesis on under‐ice lake ecology, including 36 abiotic and biotic variables from 42 research groups and 101 lakes, examining seasonal differences and connections as well as how seasonal differences vary with geophysical factors. Plankton were more abundant under ice than expected; mean winter values were 43.2% of summer values for chlorophyll a , 15.8% of summer phytoplankton biovolume and 25.3% of summer zooplankton density. Dissolved nitrogen concentrations were typically higher during winter, and these differences were exaggerated in smaller lakes. Lake size also influenced winter‐summer patterns for dissolved organic carbon ( DOC ), with higher winter DOC in smaller lakes. At coarse levels of taxonomic aggregation, phytoplankton and zooplankton community composition showed few systematic differences between seasons, although literature suggests that seasonal differences are frequently lake‐specific, species‐specific, or occur at the level of functional group. Within the subset of lakes that had longer time series, winter influenced the subsequent summer for some nutrient variables and zooplankton biomass.

Attentional function and basal forebrain cholinergic neuron morphology during aging in the Ts65Dn mouse model of Down syndrome - Brian E. Powers; Ramon Velazquez; Christy M. Kelley; Jessica A. Ash; Myla S. Strawderman; Melissa J. Alldred; Stephen D. Ginsberg; Elliott J. Mufson; Barbara J. Strupp (Brain Structure and Function, 2016)

Contribution of lianas to plant area index and canopy structure in a Panamanian forest - M. Elizabeth Rodríguez‐Ronderos; Gil Bohrer; Arturo Sanchez‐Azofeifa; Jennifer S. Powers; Stefan A. Schnitzer (Ecology, 2016)
Lianas are an important component of tropical forests, where they reduce tree growth, fecundity, and survival. Competition for light from lianas may be intense; however, the amount of light that lianas intercept is poorly understood. We used a large‐scale liana‐removal experiment to quantify light interception by lianas in a Panamanian secondary forest. We measured the change in plant area index ( PAI ) and forest structure before and after cutting lianas (for 4 yr) in eight 80 m × 80 m plots and eight control plots (16 plots total). We used ground‐based Li DAR to measure the 3‐dimensional canopy structure before cutting lianas, and then annually for 2 yr afterwards. Six weeks after cutting lianas, mean plot PAI was 20% higher in control vs. liana removal plots. One yr after cutting lianas, mean plot PAI was ~17% higher in control plots. The differences between treatments diminished significantly 2 yr after liana cutting and, after 4 yr, trees had fully compensated for liana removal. Ground‐based Li DAR revealed that lianas attenuated light in the upper‐ and middle‐forest canopy layers, and not only in the upper canopy as was previously suspected. Thus, lianas compete with trees by intercepting light in the upper‐ and mid‐canopy of this forest.

Regulation of quantal currents determines synaptic strength at neuromuscular synapses in larval Drosophila - Andrew S. Powers; Jeffrey Grizzaffi; Richard Ribchester; Gregory A. Lnenicka (Pflügers Archiv - European Journal of Physiology, 2016)

Burbot and large hydropower in North America: benefits, threats and research needs for mitigation - P. M. Harrison; L. F. G. Gutowsky; E. G. Martins; D. A. Patterson; S. J. Cooke; M. Power (Fisheries Management and Ecology, 2016)
In North America, burbot Lota lota (L.), interactions with hydropower are common, southern burbot populations are endangered and hydropower has been implicated in the decline. Thus, the objectives of this review were to identify threats and benefits of hydropower to riverine and reservoir dwelling burbot, assess overall impacts and identify key research needs for mitigation. Review findings suggest that while winter hydropower discharge regimes threaten riverine burbot spawning, burbot often successfully exploit reservoir environments. Further, while turbine entrainment has been hypothesised as a factor in the decline of burbot populations, low adult vulnerability to passage and a high resilience to juvenile removals likely mean risk to populations is low. Identified research needs include better definitions of flow and temperature requirements for riverine burbot and a quantification of the potential for reservoirs to act as source populations for downstream impacted zones. This review highlights the Pacific watershed focus of existing work and calls for status assessments and ecological research of burbot in North American Arctic and Atlantic watersheds where large hydropower and burbot interactions are common yet rarely studied.

Forest composition modifies litter dynamics and decomposition in regenerating tropical dry forest - Erik M. Schilling; Bonnie G. Waring; Jonathan S. Schilling; Jennifer S. Powers (Oecologia, 2016)

Using models to guide field experiments: a priori predictions for the CO 2 response of a nutrient‐ and water‐limited native Eucalypt woodland - Belinda E. Medlyn; Martin G. De Kauwe; Sönke Zaehle; Anthony P. Walker; Remko A. Duursma; Kristina Luus; Mikhail Mishurov; Bernard Pak; Benjamin Smith; Ying‐Ping Wang; Xiaojuan Yang; Kristine Y. Crous; et al. (Global Change Biology, 2016)
The response of terrestrial ecosystems to rising atmospheric CO 2 concentration (C a ), particularly under nutrient‐limited conditions, is a major uncertainty in Earth System models. The Eucalyptus Free‐Air CO 2 Enrichment (Euc FACE ) experiment, recently established in a nutrient‐ and water‐limited woodland presents a unique opportunity to address this uncertainty, but can best do so if key model uncertainties have been identified in advance. We applied seven vegetation models, which have previously been comprehensively assessed against earlier forest FACE experiments, to simulate a priori possible outcomes from Euc FACE . Our goals were to provide quantitative projections against which to evaluate data as they are collected, and to identify key measurements that should be made in the experiment to allow discrimination among alternative model assumptions in a postexperiment model intercomparison. Simulated responses of annual net primary productivity ( NPP ) to elevated C a ranged from 0.5 to 25% across models. The simulated reduction of NPP during a low‐rainfall year also varied widely, from 24 to 70%. Key processes where assumptions caused disagreement among models included nutrient limitations to growth; feedbacks to nutrient uptake; autotrophic respiration; and the impact of low soil moisture availability on plant processes. Knowledge of the causes of variation among models is now guiding data collection in the experiment, with the expectation that the experimental data can optimally inform future model improvements.

Trophic variability of Arctic fishes in the Canadian Beaufort Sea: a fatty acids and stable isotopes approach - Carolina Giraldo; Ashley Stasko; Emily S. Choy; Bruno Rosenberg; Andrew Majewski; Michael Power; Heidi Swanson; Lisa Loseto; James D. Reist (Polar Biology, 2016)

Temporal plasticity in thermal‐habitat selection of burbot Lota lota a diel‐migrating winter‐specialist - P. M. Harrison; L. F. G. Gutowsky; E. G. Martins; D. A. Patterson; S. J. Cooke; M. Power (Journal of Fish Biology, 2016)
In this study, animal‐borne telemetry with temperature sensors was coupled with extensive habitat temperature monitoring in a dimictic reservoir, to test the following hypotheses: behavioural thermoregulation occurs throughout the year and temperature selection varies on a diel and seasonal basis, in a winter‐specialist diel‐migrating fish. Burbot Lota lota demonstrated nightly behavioural thermoregulation throughout the year, with a large seasonal shift between selection for very cold temperatures ( L. lota avoided habitats warmer than optimal for reproduction and feeding during the spawning and non‐reproductive periods, respectively, active selection was limited to selection for 4–6° C habitat during the prespawning period. Although behavioural thermoregulation explained the night‐time migration, behavioural thermoregulation only partially explained daytime behaviour, indicating that diel migration is best explained by a combination of factors. Thus, thermal‐habitat selection was a good predictor of night‐time habitat occupancy in a diel‐migrating species. Together, these results show that thermal‐habitat selection by fishes may be important throughout the year and a more seasonally plastic behaviour than previously recognized.

Shifting grassland plant community structure drives positive interactive effects of warming and diversity on aboveground net primary productivity - Jane M. Cowles; Peter D. Wragg; Alexandra J. Wright; Jennifer S. Powers; David Tilman (Global Change Biology, 2016)
Ecosystems worldwide are increasingly impacted by multiple drivers of environmental change, including climate warming and loss of biodiversity. We show, using a long‐term factorial experiment, that plant diversity loss alters the effects of warming on productivity. Aboveground primary productivity was increased by both high plant diversity and warming, and, in concert, warming (≈1.5 °C average above and belowground warming over the growing season) and diversity caused a greater than additive increase in aboveground productivity. The aboveground warming effects increased over time, particularly at higher levels of diversity, perhaps because of warming‐induced increases in legume and C4 bunch grass abundances, and facilitative feedbacks of these species on productivity. Moreover, higher plant diversity was associated with the amelioration of warming‐induced environmental conditions. This led to cooler temperatures, decreased vapor pressure deficit, and increased surface soil moisture in higher diversity communities. Root biomass (0–30 cm) was likewise consistently greater at higher plant diversity and was greater with warming in monocultures and at intermediate diversity, but at high diversity warming had no detectable effect. This may be because warming increased the abundance of legumes, which have lower root : shoot ratios than the other types of plants. In addition, legumes increase soil nitrogen (N) supply, which could make N less limiting to other species and potentially decrease their investment in roots. The negative warming × diversity interaction on root mass led to an overall negative interactive effect of these two global change factors on the sum of above and belowground biomass, and thus likely on total plant carbon stores. In total, plant diversity increased the effect of warming on aboveground net productivity and moderated the effect on root mass. These divergent effects suggest that warming and changes in plant diversity are likely to have both interactive and divergent impacts on various aspects of ecosystem functioning.

Lianas suppress seedling growth and survival of 14 tree species in a Panamanian tropical forest - Laura Martínez‐Izquierdo; María M. García; Jennifer S. Powers; Stefan A. Schnitzer (Ecology, 2016)
Lianas are a common plant growth form in tropical forests, where they compete intensely with trees, decreasing tree recruitment, growth, and survival. If the detrimental effects of lianas vary significantly with tree species identity, as is often assumed, then lianas may influence tree species diversity and community composition. Furthermore, recent studies have shown that liana abundance and biomass are increasing relative to trees in neotropical forests, which will likely magnify the detrimental effects of lianas and may ultimately alter tree species diversity, relative abundances, and community composition. Few studies, however, have tested the responses of multiple tree species to the presence of lianas in robust, well‐replicated experiments. We tested the hypotheses that lianas reduce tree seedling growth and survival, and that the effect of lianas varies with tree species identity. We used a large‐scale liana removal experiment in Central Panama in which we planted 14 replicate seedlings of 14 different tree species that varied in shade tolerance in each of 16 80 × 80 m plots (eight liana‐removal and eight unmanipulated controls; 3136 total seedlings). Over a nearly two‐yr period, we found that tree seedlings survived 75% more, grew 300% taller, and had twice the aboveground biomass in liana‐removal plots than seedlings in control plots, consistent with strong competition between lianas and tree seedlings. There were no significant differences in the response of tree species to liana competition (i.e., there was no species by treatment interaction), indicating that lianas had a similar negative effect on all 14 tree species. Furthermore, the effect of lianas did not vary with tree species shade tolerance classification, suggesting that the liana effect was not solely based on light. Based on these findings, recently observed increases in liana abundance in neotropical forests will substantially reduce tree regeneration, but will not significantly alter tropical tree species diversity, relative abundance, or community composition.

An analysis of P seudomonas genomic diversity in take‐all infected wheat fields reveals the lasting impact of wheat cultivars on the soil microbiota - T. H. Mauchline; D. Chedom‐Fotso; G. Chandra; T. Samuels; N. Greenaway; A. Backhaus; V. McMillan; G. Canning; S. J. Powers; K. E. Hammond‐Kosack; P. R. Hirsch; I. M. Clark; et al. (Environmental Microbiology, 2015)
Summary Manipulation of the soil microbiota associated with crop plants has huge promise for the control of crop pathogens. However, to fully realize this potential we need a better understanding of the relationship between the soil environment and the genes and phenotypes that enable microbes to colonize plants and contribute to biocontrol. A recent 2 years of investigation into the effect of wheat variety on second year crop yield in the context of take‐all fungal infection presented the opportunity to examine soil microbiomes under closely defined field conditions. Amplicon sequencing of second year soil samples showed that P seudomonas spp. were particularly affected by the wheat cultivar grown in year one. Consequently, 318 rhizosphere‐associated P seudomonas fluorescens strains were isolated and characterized across a variety of genetic and phenotypic traits. Again, the wheat variety grown in the first year of the study was shown to exert considerable selective pressure on both the extent and nature of P seudomonas genomic diversity. Furthermore, multiple significant correlations were identified within the phenotypic/genetic structure of the Pseudomonas population, and between individual genotypes and the external wheat field environment. The approach outlined here has considerable future potential for our understanding of plant–microbe interactions, and for the broader analysis of complex microbial communities.

Nitrogen, phosphorus, and cation use efficiency in stands of regenerating tropical dry forest - Bonnie G. Waring; Justin M. Becknell; Jennifer S. Powers (Oecologia, 2015)

Fish community dynamics following dam removal in a fragmented agricultural stream - Matthew S. Kornis; Brian C. Weidel; Stephen M. Powers; Matthew W. Diebel; Timothy J. Cline; Justin M. Fox; James F. Kitchell (Aquatic Sciences, 2015)

Predators, host abundance, and host spatial distribution affect the movement of wingless non-colonizing vector Rhopalosiphum padi (L.) and PVY prevalence in an oat/potato system - Suzi B. Claflin; Jennifer S. Thaler; Alison G. Power (Arthropod-Plant Interactions, 2015)

Biological potential of four indigenous tree species from seasonally dry tropical forest for soil restoration - Eliane Ceccon; Itzel Sánchez; Jennifer S. Powers (Agroforestry Systems, 2015)

Erratum to: Data sources for identifying low-income, uninsured populations: application to public health—National Breast and Cervical Cancer Early Detection Program - Lucinda P. Dalzell; Florence K. L. Tangka; David S. Powers; Brett J. O’Hara; Walter Holmes; Kristy Joseph; Janet Royalty (Cancer Causes & Control, 2015)

Data sources for identifying low-income, uninsured populations: application to public health—National Breast and Cervical Cancer Early Detection Program - Lucinda P. Dalzell; Florence K. L. Tangka; David S. Powers; Brett J. O’Hara; Walter Holmes; Kristy Joseph; Janet Royalty (Cancer Causes & Control, 2015)

Acidification effects on biofouling communities: winners and losers - Lloyd S. Peck; Melody S. Clark; Deborah Power; João Reis; Frederico M. Batista; Elizabeth M. Harper (Global Change Biology, 2015)
How ocean acidification affects marine life is a major concern for science and society. However, its impacts on encrusting biofouling communities, that are both the initial colonizers of hard substrata and of great economic importance, are almost unknown. We showed that community composition changed significantly, from 92% spirorbids, 3% ascidians and 4% sponges initially to 47% spirorbids, 23% ascidians and 29% sponges after 100 days in acidified conditions (pH 7.7). In low pH, numbers of the spirorbid Neodexiospira pseudocorrugata were reduced ×5 compared to controls. The two ascidians present behaved differently with Aplidium sp. decreasing ×10 in pH 7.7, whereas Molgula sp. numbers were ×4 higher in low pH than controls. Calcareous sponge ( Leucosolenia sp.) numbers increased ×2.5 in pH 7.7 over controls. The diatom and filamentous algal community was also more poorly developed in the low pH treatments compared to controls. Colonization of new surfaces likewise showed large decreases in spirorbid numbers, but numbers of sponges and Molgula sp. increased. Spirorbid losses appeared due to both recruitment failure and loss of existing tubes. Spirorbid tubes are comprised of a loose prismatic fabric of calcite crystals. Loss of tube materials appeared due to changes in the binding matrix and not crystal dissolution, as SEM analyses showed crystal surfaces were not pitted or dissolved in low pH conditions. Biofouling communities face dramatic future changes with reductions in groups with hard exposed exoskeletons and domination by soft‐bodied ascidians and sponges.

Far-Field Tsunami Hazard in New Zealand Ports - Jose C. Borrero; Derek G. Goring; S. Dougal Greer; William L. Power (Pure and Applied Geophysics, 2015)

The influence of seasonality and species effects on surface fine roots and nodulation in tropical legume tree plantations - Maria G. Gei; Jennifer S. Powers (Plant and Soil, 2015)

Data dialogues: critical connections for designing and implementing future nanomaterial research - Christina M. Powers; Khara D. Grieger; Christian Beaudrie; Christine Ogilvie Hendren; J. Michael Davis; Amy Wang; Christie M. Sayes; Margaret MacDonell; Jeffrey S. Gift (Environment Systems and Decisions, 2015)

Liana competition with tropical trees varies seasonally but not with tree species identity - Leonor Álvarez-Cansino; Stefan A. Schnitzer; Joseph P. Reid; Jennifer S. Powers (Ecology, 2015)
Lianas in tropical forests compete intensely with trees for above‐ and belowground resources and limit tree growth and regeneration. Liana competition with adult canopy trees may be particularly strong, and, if lianas compete more intensely with some tree species than others, they may influence tree species composition. We performed the first systematic, large‐scale liana removal experiment to assess the competitive effects of lianas on multiple tropical tree species by measuring sap velocity and growth in a lowland tropical forest in Panama. Tree sap velocity increased 60% soon after liana removal compared to control trees, and tree diameter growth increased 25% after one year. Although tree species varied in their response to lianas, this variation was not significant, suggesting that lianas competed similarly with all tree species examined. The effect of lianas on tree sap velocity was particularly strong during the dry season, when soil moisture was low, suggesting that lianas compete intensely with trees for water. Under the predicted global change scenario of increased temperature and drought intensity, competition from lianas may become more prevalent in seasonal tropical forests, which, according to our data, should have a negative effect on most tropical tree species.

Genetic diversity, population structure and phenotypic variation in European Salix viminalis L. (Salicaceae) - S. Berlin; S. O. Trybush; J. Fogelqvist; N. Gyllenstrand; H. R. Hallingbäck; I. Åhman; N-E. Nordh; I. Shield; S. J. Powers; M. Weih; U. Lagercrantz; A-C. Rönnberg-Wästljung; et al. (Tree Genetics & Genomes, 2014)

Plant and arthropod community sensitivity to rainfall manipulation but not nitrogen enrichment in a successional grassland ecosystem - Mark A. Lee; Pete Manning; Catherine S. Walker; Sally A. Power (Oecologia, 2014)

Positive and Negative Effects of a Threatened Parrotfish on Reef Ecosystems - DOUGLAS J. MCCAULEY; HILLARY S. YOUNG; ROGER GUEVARA; GARETH J. WILLIAMS; ELEANOR A. POWER; ROBERT B. DUNBAR; DOUGLAS W. BIRD; WILLIAM H. DURHAM; FIORENZA MICHELI (Conservation Biology, 2014)
Species that are strong interactors play disproportionately important roles in the dynamics of natural ecosystems. It has been proposed that their presence is necessary for positively shaping the structure and functioning of ecosystems. We evaluated this hypothesis using the case of the world's largest parrotfish ( Bolbometopon muricatum ), a globally imperiled species. We used direct observation, animal tracking, and computer simulations to examine the diverse routes through which B. muricatum affects the diversity, dispersal, relative abundance, and survival of the corals that comprise the foundation of reef ecosystems. Our results suggest that this species can influence reef building corals in both positive and negative ways. Field observation and simulation outputs indicated that B. muricatum reduced the abundance of macroalgae that can outcompete corals, but they also feed directly on corals, decreasing coral abundance, diversity, and colony size. B. muricatum appeared to facilitate coral advancement by mechanically dispersing coral fragments and opening up bare space for coral settlement, but they also damaged adult corals and remobilized a large volume of potentially stressful carbonate sediment. The impacts this species has on reefs appears to be regulated in part by its abundance—the effects of B. muricatum were more intense in simulation scenarios populated with high densities of these fish. Observations conducted in regions with high and low predator (e.g., sharks) abundance generated results that are consistent with the hypothesis that these predators of B. muricatum may play a role in governing their abundance; thus, predation may modulate the intensity of the effects they have on reef dynamics. Overall our results illustrate that functionally unique and threatened species may not have universally positive impacts on ecosystems and that it may be necessary for environmental managers to consider the diverse effects of such species and the forces that mediate the strength of their influence. Efectos Positivos y Negativos de un Pez Loro Amenazado Sobre Ecosistemas Arrecifales

Proteomic Approach to Skin Regeneration in a Marine Teleost: Modulation by Oestradiol-17β - Antoni Ibarz; Patricia I. S. Pinto; Deborah M. Power (Marine Biotechnology, 2013)

Acrylamide concentrations in potato crisps in Europe from 2002 to 2011 - Stephen J. Powers; Donald S. Mottram; Andrew Curtis; Nigel G. Halford (Food Additives & Contaminants: Part A, 2013)

Observations, Effects and Real Time Assessment of the March 11, 2011 Tohoku-oki Tsunami in New Zealand - Jose C. Borrero; Rob Bell; Claudia Csato; Willem DeLange; Derek Goring; S. Dougal Greer; Vernon Pickett; William Power (Pure and Applied Geophysics, 2013)

Water absorption and bicarbonate secretion in the intestine of the sea bream are regulated by transmembrane and soluble adenylyl cyclase stimulation - Edison S. M. Carvalho; Sílvia F. Gregório; Deborah M. Power; Adelino V. M. Canário; Juan Fuentes (Journal of Comparative Physiology B, 2012)

Current evidence for human yersiniosis in Ireland - T. Ringwood; B. P. Murphy; N. Drummond; J. F. Buckley; A. P. Coveney; H. P. Redmond; J. P. Power; S. Fanning; M. B. Prentice (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Global major histocompatibility Class II β (mh‐IIβ) ‐polymorphism in Arctic charr Salvelinus alpinus - P. Conejeros; M. Power; S. Alekseyev; B. Dixon (Journal of Fish Biology, 2012)
This study explored the use of the gene encoding the β subunit of the major histocompatibility (MH) receptor as a population marker in Arctic charr Salvelinus alpinus . The use of this polymorphic marker allowed differentiation of the S. alpinus lineages previously defined using mitochondrial DNA (mtDNA) but also allowed differentiation between the populations studied within those lineages. The majority of the variation observed here occurred prior to the last glaciation event. Nevertheless, all S. alpinus populations were differentiated using both MH Class II β ( mh‐IIβ ) sequences and allelic frequencies. The fact that all the populations studied presented high rates of non‐synonymous: synonymous substitutions and high levels of interpopulation variation, suggested mh‐IIβ as an ideal marker to assess differentiation among S. alpinus populations in ways that may represent divergence both by genetic drift and natural adaptation to the local environment.

Variable Responses of Lowland Tropical Forest Nutrient Status to Fertilization and Litter Manipulation - Emma J. Sayer; S. Joseph Wright; Edmund V. J. Tanner; Joseph B. Yavitt; Kyle E. Harms; Jennifer S. Powers; Michael Kaspari; Milton N. Garcia; Benjamin L. Turner (Ecosystems, 2012)

Non-cancer endpoints in BRCA1/2 carriers after risk-reducing salpingo-oophorectomy - J. V. Cohen; L. Chiel; L. Boghossian; M. Jones; J. E. Stopfer; J. Powers; T. R. Rebbeck; K. L. Nathanson; S. M. Domchek (Familial Cancer, 2012)

Forest Management, Engineering, and Operations - Randy Kolka; Matt Powers; John Bradford; Brian Palik; Marty Jurgensen; Dalia Abbas; Tom Gallagher; Stephen Ambagis; Finto Antony; Lewis Jordan; Richard Daniels; Laurie Schimleck; et al. (Journal of Forestry, 2011)
9Forests represent a major global C sink, and forest management strategies that maximize carbon storage offer one avenue for mitigating increases in atmospheric carbon dioxide concentrations. Our understanding of relationships between forest management, productivity, carbon storage, and stand age, however, is limited. We established research plots in a chronosequence of thinned and unmanaged red pine stands in northern Minnesota to study patterns of carbon storage, and the major fluxes that influence carbon sequestration. We completed an inventory of all major C pools across a chronosequence of 57 red pine stands ages 9-306 years on the Chippewa National Forest in the fall of 2009. Results indicate total ecosystem C pools increase as red pine stands age for at least 150 years, and on-site C storage in thinned stands appears similar to unmanaged stands of comparable ages, despite different age-related trends in the live tree and forest floor pools. Thinned stands may have the potential to store more C than unmanaged stands in old age when C removed during harvesting is added into the total ecosystem C pool.

Macro- and micronutrient effects on decomposition of leaf litter from two tropical tree species: inferences from a short-term laboratory incubation - Jennifer S. Powers; Stefani Salute (Plant and Soil, 2011)

Red snapper management in the Gulf of Mexico: science- or faith-based? - J. H. Cowan; C. B. Grimes; W. F. Patterson; C. J. Walters; A. C. Jones; W. J. Lindberg; D. J. Sheehy; W. E. Pine; J. E. Powers; M. D. Campbell; K. C. Lindeman; S. L. Diamond; et al. (Reviews in Fish Biology and Fisheries, 2011)

New perspectives on the energy return on (energy) investment (EROI) of corn ethanol - David J. Murphy; Charles A. S. Hall; Bobby Powers (Environment, Development and Sustainability, 2011)

Effects of the novel endocannabinoid uptake inhibitor, LY2183240, on fear-potentiated startle and alcohol-seeking behaviors in mice selectively bred for high alcohol preference - Matthew S. Powers; Gustavo D. Barrenha; Nate S. Mlinac; Eric L. Barker; Julia A. Chester (Psychopharmacology, 2010)

Survivorship and development of the banana weevil Cosmopolites sordidus (Coleoptera: Curculionidae) on different banana cultivars in Uganda - Gertrude Night; Clifford S. Gold; Alison G. Power (International Journal of Tropical Insect Science, 2010)

Leaf traits and water relations of 12 evergreen species in Costa Rican wet and dry forests: patterns of intra-specific variation across forests and seasons - Sybil G. Gotsch; Jennifer S. Powers; Manuel T. Lerdau (Plant Ecology, 2010)

Estimates of EPSP amplitude based on changes in motoneuron discharge rate and probability - Randall K. Powers; K. S. Türker (Experimental Brain Research, 2010)

Epidemiology of non-multiresistant methicillin-resistant Staphylococcus aureus infection in Queensland, Australia: associations with indigenous populations and Panton–Valentine leukocidin - G. R. Nimmo; J. M. Schooneveldt; J. L. Sutherland; S. Power; D. Olesen; C. Selvey; F. Beard; M. Jones; D. L. Paterson (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Survivorship and development rates of banana weevils reared on excised plant material of different banana cultivars - Gertrude Night; Clifford S. Gold; Alison G. Power (International Journal of Tropical Insect Science, 2010)

Tyrosine hydroxylase, chromogranin A, and steroidogenic acute regulator as markers for successful separation of human adrenal medulla - Stephanie M. J. Fliedner; Jan Breza; Richard Kvetnansky; James F. Powers; Arthur S. Tischler; Robert Wesley; Maria Merino; Hendrik Lehnert; Karel Pacak (Cell and Tissue Research, 2010)

Ultrasequencing of the meiofaunal biosphere: practice, pitfalls and promises - S. CREER; V. G. FONSECA; D. L. PORAZINSKA; R. M. GIBLIN‐DAVIS; W. SUNG; D. M. POWER; M. PACKER; G. R. CARVALHO; M. L. BLAXTER; P. J. D. LAMBSHEAD; W. K. THOMAS (Molecular Ecology, 2010)
Biodiversity assessment is the key to understanding the relationship between biodiversity and ecosystem functioning, but there is a well‐acknowledged biodiversity identification gap related to eukaryotic meiofaunal organisms. Meiofaunal identification is confounded by the small size of taxa, morphological convergence and intraspecific variation. However, the most important restricting factor in meiofaunal ecological research is the mismatch between diversity and the number of taxonomists that are able to simultaneously identify and catalogue meiofaunal diversity. Accordingly, a molecular operational taxonomic unit (MOTU)‐based approach has been advocated for en mass meiofaunal biodiversity assessment, but it has been restricted by the lack of throughput afforded by chain termination sequencing. Contemporary pyrosequencing offers a solution to this problem in the form of environmental metagenetic analyses, but this represents a novel field of biodiversity assessment. Here, we provide an overview of meiofaunal metagenetic analyses, ranging from sample preservation and DNA extraction to PCR, sequencing and the bioinformatic interrogation of multiple, independent samples using 454 Roche sequencing platforms. We report two examples of environmental metagenetic nuclear small subunit 18S (nSSU) analyses of marine and tropical rainforest habitats and provide critical appraisals of the level of putative recombinant DNA molecules (chimeras) in metagenetic data sets. Following stringent quality control measures, environmental metagenetic analyses achieve MOTU formation across the eukaryote domain of life at a fraction of the time and cost of traditional approaches. The effectiveness of Roche 454 sequencing brings substantial advantages to studies aiming to elucidate the molecular genetic richness of not only meiofaunal, but also all complex eukaryotic communities.

Phylogeography and sympatric differentiation of the Arctic charr Salvelinus alpinus (L.) complex in Siberia as revealed by mtDNA sequence analysis - S. S. Alekseyev; R. Bajno; N. V. Gordeeva; J. D. Reist; M. Power; A. F. Kirillov; V. P. Samusenok; A. N. Matveev (Journal of Fish Biology, 2009)
Sequence variation in the mtDNA control region of Arctic charr Salvelinus alpinus and Dolly Varden Salvelinus malma from 56 Siberian and North American populations was analysed to assess their phylogeographic relationships and the origins of sympatric forms. Phylogenetic trees confirm the integrity of phylogroups reported in previous mtDNA studies except that the Siberian group does not separate as a single cluster. Haplotype network analysis indicates the proximity of Siberian and Atlantic haplotypes. These are considered as one Eurasian group represented by the Atlantic, east Siberian (interior Siberia including Transbaikalia, Taimyr) and Eurosiberian (Finland, Spitsbergen, Taimyr) sub‐groups. Salvelinus alpinus with presumably introgressed Bering group (malma) haplotypes were found along eastern Siberian coasts up to the Olenek Bay and the Lena Delta region, where they overlap with the Eurasian group and in the easternmost interior region. It is proposed that Siberia was colonized by S. alpinus in two stages: from the west by the Eurasian group and later from the east by the Bering group. The high diversity of Eurasian group haplotypes in Siberia indicates its earlier colonization by S. alpinus as compared with the European Alps. This colonization was rapid, proceeded from a diverse gene pool, and was followed by differential survival of ancestral mtDNA lineages in different basins and regions, and local mutational events in isolated populations. The results presented here support a northern origin of Transbaikalian S. alpinus , the dispersion of S. alpinus to the Lake Baikal Basin from the Lena Basin, segregation of S. alpinus between Lena tributaries and their restricted migration over the divides between sub‐basins. These results also support sympatric origin of intralacustrine forms of S. alpinus .

Tropical nematode diversity: vertical stratification of nematode communities in a Costa Rican humid lowland rainforest - T. O. POWERS; D. A. NEHER; P. MULLIN; A. ESQUIVEL; R. M. GIBLIN‐DAVIS; N. KANZAKI; S. P. STOCK; M. M. MORA; L. URIBE‐LORIO (Molecular Ecology, 2009)
Comparisons of nematode communities among ecosystems have indicated that, unlike many organisms, nematode communities have less diversity in the tropics than in temperate ecosystems. There are, however, few studies of tropical nematode diversity on which to base conclusions of global patterns of diversity. This study reports an attempt to estimate nematode diversity in the lowland tropical rainforest of La Selva Biological Research Station in Costa Rica. We suggest one reason that previous estimates of tropical nematode diversity were low is because habitats above the mineral soil are seldom sampled. As much as 62% of the overall genetic diversity, measured by an 18S ribosomal barcode, existed in litter and understorey habitats and not in soil. A maximum‐likelihood tree of barcodes from 360 individual nematodes indicated most major terrestrial nematode lineages were represented in the samples. Estimated ‘species’ richness ranged from 464 to 502 within the four 40 × 40 m plots. Directed sampling of insects and their associated nematodes produced a second set of barcodes that were not recovered by habitat sampling, yet may constitute a major class of tropical nematode diversity. While the generation of novel nematode barcodes proved relatively easy, their identity remains obscure due to deficiencies in existing taxonomic databases. Specimens of Criconematina, a monophyletic group of soil‐dwelling plant‐parasitic nematodes were examined in detail to assess the steps necessary for associating barcodes with nominal species. Our results highlight the difficulties associated with studying poorly understood organisms in an understudied ecosystem using a destructive (i.e. barcode) sampling method.

Stoichiometry of soil enzyme activity at global scale - Robert L. Sinsabaugh; Christian L. Lauber; Michael N. Weintraub; Bony Ahmed; Steven D. Allison; Chelsea Crenshaw; Alexandra R. Contosta; Daniela Cusack; Serita Frey; Marcy E. Gallo; Tracy B. Gartner; Sarah E. Hobbie; et al. (Ecology Letters, 2008)
Extracellular enzymes are the proximate agents of organic matter decomposition and measures of these activities can be used as indicators of microbial nutrient demand. We conducted a global‐scale meta‐analysis of the seven‐most widely measured soil enzyme activities, using data from 40 ecosystems. The activities of β‐1,4‐glucosidase, cellobiohydrolase, β‐1,4‐ N ‐acetylglucosaminidase and phosphatase g −1 soil increased with organic matter concentration; leucine aminopeptidase, phenol oxidase and peroxidase activities showed no relationship. All activities were significantly related to soil pH. Specific activities, i.e. activity g −1 soil organic matter, also varied in relation to soil pH for all enzymes. Relationships with mean annual temperature (MAT) and precipitation (MAP) were generally weak. For hydrolases, ratios of specific C, N and P acquisition activities converged on 1 : 1 : 1 but across ecosystems, the ratio of C : P acquisition was inversely related to MAP and MAT while the ratio of C : N acquisition increased with MAP. Oxidative activities were more variable than hydrolytic activities and increased with soil pH. Our analyses indicate that the enzymatic potential for hydrolyzing the labile components of soil organic matter is tied to substrate availability, soil pH and the stoichiometry of microbial nutrient demand. The enzymatic potential for oxidizing the recalcitrant fractions of soil organic material, which is a proximate control on soil organic matter accumulation, is most strongly related to soil pH. These trends provide insight into the biogeochemical processes that create global patterns in ecological stoichiometry and organic matter storage.

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Over-expression of a gibberellin 2-oxidase gene from Phaseolus coccineus L. enhances gibberellin inactivation and induces dwarfism in Solanum species - C. Dijkstra; E. Adams; A. Bhattacharya; A. F. Page; P. Anthony; S. Kourmpetli; J. B. Power; K. C. Lowe; S. G. Thomas; P. Hedden; A. L. Phillips; M. R. Davey (Plant Cell Reports, 2008)

Phylogenetic analysis of Rhizoctonia solani subgroups associated with web blight symptoms on common bean based on ITS-5.8S rDNA - G. Godoy-Lutz; S. Kuninaga; J. R. Steadman; K. Powers (Journal of General Plant Pathology, 2008)

13C labeling of plant assimilates using a simple canopy-scale open air system - Alan F. Talhelm; Samir A. Qadir; Matthew D. Powers; Kate L. Bradley; Alexander L. Friend; Kurt S. Pregitzer (Plant and Soil, 2007)

Occurrence of Cryptosporidium parvum and Bacterial Pathogens in Faecal Material in the Red Fox (Vulpes vulpes) Population - Y. Nagano; M. B. Finn; C. J. Lowery; T. Murphy; J. Moriarty; E. Power; D. Toolan; A. O’Loughlin; M. Watabe; K. A. McCorry; E. Crothers; J. S. G. Dooley; et al. (Veterinary Research Communications, 2007)

NeuroAIDS, Drug Abuse, and Inflammation: Building Collaborative Research Activities - Joan W. Berman; Monica J. Carson; Linda Chang; Brian M. Cox; Howard S. Fox; R. Gilberto Gonzalez; Glen R. Hanson; Kurt F. Hauser; Wen-Zhe Ho; Jau-Shyong Hong; Eugene O. Major; William F. Maragos; et al. (Journal of Neuroimmune Pharmacology, 2006)

Spatial variation of soil organic carbon concentrations and stable isotopic composition in 1-ha plots of forest and pasture in Costa Rica: implications for the natural abundance technique - Jennifer S. Powers (Biology and Fertility of Soils, 2006)

Comparative field performance over 3 years and two sites of transgenic wheat lines expressing HMW subunit transgenes - Peter R. Shewry; Stephen Powers; J. Michael Field; Roger J. Fido; Huw D. Jones; Gillian M. Arnold; Jevon West; Paul A. Lazzeri; Pilar Barcelo; Francisco Barro; Arthur S. Tatham; Frank Bekes; et al. (Theoretical and Applied Genetics, 2006)

Biotic interactions and plant invasions - Charles E. Mitchell; Anurag A. Agrawal; James D. Bever; Gregory S. Gilbert; Ruth A. Hufbauer; John N. Klironomos; John L. Maron; William F. Morris; Ingrid M. Parker; Alison G. Power; Eric W. Seabloom; Mark E. Torchin; et al. (Ecology Letters, 2006)
Introduced plant populations lose interactions with enemies, mutualists and competitors from their native ranges, and gain interactions with new species, under new abiotic conditions. From a biogeographical perspective, differences in the assemblage of interacting species, as well as in abiotic conditions, may explain the demographic success of the introduced plant populations relative to conspecifics in their native range. Within invaded communities, the new interactions and conditions experienced by the invader may influence both its demographic success and its effects on native biodiversity. Here, we examine indirect effects involving enemies, mutualists and competitors of introduced plants, and effects of abiotic conditions on biotic interactions. We then synthesize ideas building on Darwin's idea that the kinds of new interactions gained by an introduced population will depend on its relatedness to native populations. This yields a heuristic framework to explain how biotic interactions and abiotic conditions influence invader success. We conclude that species introductions generally alter plants’ interactions with enemies, mutualists and competitors, and that there is increasing evidence that these altered interactions jointly influence the success of introduced populations.

International Trends in Bioassay Use for Effluent Management - Elizabeth A. Power; Ruth S. Boumphrey (Ecotoxicology, 2004)

Response of Pinus Sylvestris Seedlings to Cadmium and Mycorrhizal Colonisation - C.-G. Kim; S. A. Power; J. N. B. Bell (Water, Air, & Soil Pollution, 2004)

Changes in Soil Carbon and Nitrogen after Contrasting Land-use Transitions in Northeastern Costa Rica - Jennifer S. Powers (Ecosystems, 2004)

Estimating soil carbon fluxes following land‐cover change: a test of some critical assumptions for a region in Costa Rica - Jennifer S. Powers; Jane M. Read; Julie S. Denslow; Sandra M. Guzman (Global Change Biology, 2004)
Changes in soil carbon storage that accompany land‐cover change may have significant effects on the global carbon cycle. The objective of this work was to examine how assumptions about preconversion soil C storage and the effects of land‐cover change influence estimates of regional soil C storage. We applied three models of land‐cover change effects to two maps of preconversion soil C in a 140 000 ha area of northeastern Costa Rica. One preconversion soil C map was generated using values assigned to tropical wet forest from the literature, the second used values obtained from extensive field sampling. The first model of land‐cover change effects used values that are typically applied in global assessments, the second and third models used field data but differed in how the data were aggregated (one was based on land‐cover transitions and one was based on terrain attributes). Changes in regional soil C storage were estimated for each combination of model and preconversion soil C for three time periods defined by geo‐referenced land‐cover maps. The estimated regional soil C under forest vegetation (to 0.3 m) was higher in the map based on field data (10.03 Tg C) than in the map based on literature data (8.90 Tg C), although the range of values derived from propagating estimation errors was large (7.67–12.40 Tg C). Regional soil C storage declined through time due to forest clearing for pasture and crops. Estimated CO 2 fluxes depended more on the model of land‐cover change effects than on preconversion soil C. Cumulative soil C losses (1950–1996) under the literature model of land‐cover effects exceeded estimates based on field data by factors of 3.8–8.0. In order to better constrain regional and global‐scale assessments of carbon fluxes from soils in the tropics, future research should focus on methods for extrapolating regional‐scale constraints on soil C dynamics to larger spatial and temporal scales.

Effects of soil cadmium on Pinus sylvestris L. seedlings - C.-G. Kim; J. N. B. Bell; S. A. Power (Plant and Soil, 2003)

Effects of cadmium on growth and glucose utilisation of ectomycorrhizal fungi in vitro - C.-G. Kim; S. A. Power; J. N. B. Bell (Mycorrhiza, 2003)

Effects of Cadmium and Soil Type on Mineral Nutrition and Carbon Partitioning in Seedlings of Pinus Sylvestris - C.-G. Kim; S. A. Power; J. N. B. Bell (Water, Air, & Soil Pollution, 2003)

STOIC: a study of coupled model climatology and variability in tropical ocean regions - Davey M.; Huddleston M.; Sperber K.; Braconnot P.; Bryan F.; Chen D.; Colman R.; Cooper C.; Cubasch U.; Delecluse P.; DeWitt D.; Fairhead L.; et al. (Climate Dynamics, 2002)

Molecular systematics of Solanum section Lycopersicum (Lycopersicon) using the nuclear ITS rDNA region - J. A. Marshall; S. Knapp; M. R. Davey; J. B. Power; E. C. Cocking; M. D. Bennett; A. V. Cox (Theoretical and Applied Genetics, 2001)

ENSIP: the El Niño simulation intercomparison project - M. Latif; K. Sperber; J. Arblaster; P. Braconnot; D. Chen; A. Colman; U. Cubasch; C. Cooper; P. Delecluse; D. Dewitt; L. Fairhead; G. Flato; et al. (Climate Dynamics, 2001)

Winter movements and habitat use of riverine brown trout, white sucker and common carp in relation to flooding and ice break‐up - R. S. Brown; G. Power; S. Beltaoa (Journal of Fish Biology, 2001)
Movement of radio‐tagged riverine brown trout Salmo trutta , white sucker Catostomus commersoni and common carp Cyprinus carpio in the Grand River, Ontario, was minimal during the winter except during periods of high water discharge or the break‐up of river ice. Ice break‐up and flooding occur when southern air masses penetrate northwards in winter and as air temperatures increase in spring. Both white suckers and common carp moved the longest distances, generally in a downstream direction, during flooding and ice break‐up. Brown trout moved less during these times. All three species had positive relationships between distance moved and water discharge. During periods of high water discharge and ice break‐up, white suckers and common carp used backwater habitats more and main channel habitats less than during periods of low water discharge. During high flows, brown trout tended to use runs more and pools less. The break‐up of river ice and accompanying flooding resulted in several fish being stranded on the floodplain. Backwater habitats appear to be important areas of refuge for riverine fishes during periods of flooding and ice break‐up.

Volatile Compounds from Salix spp. Varieties Differing in Susceptibility to Three Willow Beetle Species - L. Peacock; M. Lewis; S. Powers (Journal of Chemical Ecology, 2001)

Lizard diversity and agricultural disturbance in a Caribbean forest landscape - Richard E. Glor; Alexander S. Flecker; Michael F. Benard; Alison G. Power (Biodiversity and Conservation, 2001)

Applications and characteristics of angler diary programmes in Ontario, Canada - S. J. Cooke; W. I. Dunlop; D. Macclennan; G. Power (Fisheries Management and Ecology, 2000)
Angler diary programmes ( n =46, 1979–1997) implemented in Ontario by the Ontario Ministry of Natural Resources are reviewed, and the different uses of angler diary programmes, levels of participation and differences in programme design are reported. In Ontario, angler diary use is common, but successful application is limited. This review revealed a variety of uses and approaches for administering angler diary programmes. Problems arise when programmes are initiated without the complete commitment of the administrators and agency, or when there is no regular review so adaptive changes can be made. If administrators realize the potential biases and problems associated with diaries, and design programmes to control them, angler diaries can provide favorable cost‐effective results. With reduced funding and staffing constraints, angler diary programmes could become the primary method of data collection for specialized and remote fisheries.

Pheochromocytoma cell lines from heterozygous neurofibromatosis knockout mice - J. F. Powers; M. J. Evinger; P. Tsokas; S. Bedri; J. Alroy; M. Shahsavari; A. S. Tischler (Cell and Tissue Research, 2000)

Effects of hanging ice dams on winter movements and swimming activity of fish - R. S. Brown; G. Power; S. Beltaos; T. A. Beddow (Journal of Fish Biology, 2000)
Formation of a hanging dam, a large, thick sub‐surface accumulation of frazil ice that blocked river flow, altered physical environmental conditions dramatically and common carp Cyprinus carpio , and brown trout Salmo trutta , evacuated the pool in which the dam developed. A mean of 80·1% of the pool volume was filled with frazil ice. Mean and bottom water velocities in the pool increased from 6 to 27 cm s −1 and from 4 to 21 cm s −1 , respectively, when the hanging dam formed, and water depth decreased from a mean of 2·25 to 0·45 m. Activity levels of fish leaving the pool varied. Two carp had higher swimming activities when in the over wintering pool, compared to the period when they were out of it, and a third showed opposite results.

The seasonal cycle in coupled ocean-atmosphere general circulation models - C. Covey; A. Abe-Ouchi; G. J. Boer; B. A. Boville; U. Cubasch; L. Fairhead; G. M. Flato; H. Gordon; E. Guilyardi; X. Jiang; T. C. Johns; H. Le Treut; et al. (Climate Dynamics, 2000)

Combined PI–DAPI staining (CPD) reveals NOR asymmetry and facilitates karyotyping of plant chromosomes - S. C. Andras; T. P. V. Hartman; J. Alexander; R. McBride; J. A. Marshall; J. B. Power; E. C. Cocking; M. R. Davey (Chromosome Research, 2000)

Agrobacterium-mediated transformation of Lupinus mutabilis L. using shoot apical explants - Mehmet Babaoglu; Matthew S. McCabe; J. Brian Power; Michael R. Davey (Acta Physiologiae Plantarum, 2000)

Plant regeneration from embryogenic cell suspension-derived protoplasts of rubber - S. Sushamakumari; M.P. Asokan; P. Anthony; K.C. Lowe; J.B. Power; M.R. Davey (Plant Cell, Tissue and Organ Culture (PCTOC), 2000)

Central and peripheral tissue distribution of diclofenac after subcutaneous injection in the rat - R. F. Grace; S. R. Edwards; L. E. Mather; Y. Lin; I. Power (Inflammopharmacology, 2000)

Decadal climate variability simulated in a coupled general circulation model - D. J. Walland; S. B. Power; A. C. Hirst (Climate Dynamics, 2000)

A Drop-spreading Technique to Produce Cytoplasm-free Mitotic Preparations from Plants with Small Chromosomes - S. C. Andras; T. P. V. Hartman; J. A. Marshall; R. Marchant; J. B. Power; E. C. Cocking; M. R. Davey (Chromosome Research, 1999)

Effect of Single and Paired Metal Inputs in Soil on a Stress-Inducible Transgenic Nematode - R. S. Power; D. I. de Pomerai (Archives of Environmental Contamination and Toxicology, 1999)

Expression of a chimeric nitrate reductase gene in transgenic lettuce reduces nitrate in leaves - I. S. Curtis; J. B. Power; A. M. M. de Laat; M. Caboche; M. R. Davey (Plant Cell Reports, 1999)

Increased stable inheritance of herbicide resistance in transgenic lettuce carrying a petE promoter-bar gene compared with a CaMV 35S-bar gene - M. S. McCabe; F. Schepers; A. van der Arend; U. Mohapatra; A. M. M. de Laat; J. B. Power; M. R. Davey (Theoretical and Applied Genetics, 1999)

Intergeneric somatic hybrids of rice [Oryza sativa L. (+) Porteresia coarctata (Roxb.) Tateoka] - N. B. Jelodar; N. W. Blackhall; T. P. V. Hartman; D. S. Brar; G. Khush; M. R. Davey; E. C. Cocking; J. B. Power (Theoretical and Applied Genetics, 1999)

Inter-decadal modulation of the impact of ENSO on Australia - S. Power; T. Casey; C. Folland; A. Colman; V. Mehta (Climate Dynamics, 1999)

A stable transformation system for the ornamental plant, Datura meteloides D. C. - I. S. Curtis; J. B. Power; P. Hedden; D. A. Ward; A. Phillips; K. C. Lowe; M. R. Davey (Plant Cell Reports, 1999)

Expression of the Bar Gene Confers Herbicide Resistance in Transgenic Lettuce - Umaballava Mohapatra; Matthew S. McCabe; J. Brian Power; Frank Schepers; Aad Van Der Arend; Michael R. Davey (Transgenic Research, 1999)

Exercise training protects against contraction-induced lipid peroxidation in the diaphragm - Heather K. Vincent; Scott K. Powers; Haydar A. Demirel; Jeff S. Coombes; Hisashi Naito (European Journal of Applied Physiology, 1999)

Nerve growth factor receptor signaling in proliferation of normal adult rat chromaffin cells - J. F. Powers; Mehzad Shahsavari; Panayiotis Tsokas; Arthur S. Tischler (Cell and Tissue Research, 1999)

Stress-inducible transgenic nematodes as biomonitors of soil and water pollution - R S Power; H E David; M H A Z Mutwakil; K Fletcher; C Daniells; M A Nowell; J L Dennis; A Martinelli; R Wiseman; E Wharf; D I de Pomerai (Journal of Biosciences, 1998)

Immunoreactivity of normal rabbit serum with epinephrine (E) cells of the rat adrenal medulla after microwave antigen retrieval - A. S. Tischler; Panayiotis Tsokas; Mehzad Shahsavari; James F. Powers (Cell and Tissue Research, 1998)

DNA Isolation and AFLP™ Genetic Fingerprinting of shape Theobroma cacao (L.) - Matthew D. Perry; Michael R. Davey; J. Brian Power; Kenneth C. Lowe; H. Frances J. Bligh; Paul S. Roach; Chris Jones (Plant Molecular Biology Reporter, 1998)

Shoot regeneration from cultured root explants of spinach (Spinacia oleracea L.): a system for Agrobacterium transformation - K. A. Knoll; K. C. Short; I. S. Curtis; J. B. Power; M. R. Davey (Plant Cell Reports, 1997)

Perspectives of the Scientific Community on the Status of Ecological Risk Assessment - M. Power; S. M. Adams (Environmental Management, 1997)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Non-linear climate feedback analysis in an atmospheric general circulation model - R. A. Colman; S. B. Power; B. J. McAvaney (Climate Dynamics, 1997)

Eddy parametrization and the oceanic response to idealized global warming - S. B. Power; A. C. Hirst (Climate Dynamics, 1997)

Homoeologous pairing and recombination in backcross derivatives of tomato somatic hybrids [Lycopersicon esculentum (+) L. peruvianum] - A. S. Parokonny; J. A. Marshall; M. D. Bennett; E. C. Cocking; M. R. Davey; J. Brian Power (Theoretical and Applied Genetics, 1997)

To blink or not to blink: inhibition and facilitation of reflex blinks - Alice S. Powers; Edward J. Schicatano; Michele A. Basso; Craig Evinger (Experimental Brain Research, 1997)

Egg removal and intraspecific brood parasitism in the European starling (Sturnus vulgaris) - M. P. Lombardo; H. W. Power; P. C. Stouffer; Linda C. Romagnano; Ann S. Hoffenberg (Behavioral Ecology and Sociobiology, 1989)

Spectral analysis of the high-frequency electrocardiogram in contusive myocardial injury - T. D. Schick; S. R. Powers (Annals of Biomedical Engineering, 1978)